Electrode composite, electrode comprising same, all-solid-state battery comprising same, and method of manufacturing same

CN122826191APending Publication Date: 2026-09-25LG ENERGY SOLUTION LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202580007835.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-02-11
Filing Date
2025-02-19
Publication Date
2026-09-25

AI Technical Summary

Technical Problem

尽管硫化物SSE拥有优异的电化学和机械性能,但仍未见到能够实现具有高利用率、高面积容量和良好循环稳定性的实用的全固态锂硫电池的报道

Benefits of technology

[0072]Li2S活性材料在氧化为硫时显示出高活化能垒。根据本公开,将Li2S、LPS-X(如LPSCl)与碳一起球磨以活化Li2S。已发现,球磨不仅活化了Li2S,而且在球磨后导致LPS-X(如LPSCl)在XRD分析中失去其晶体峰,这是预料不到且令人惊讶的。XRD数据显示,LPSCl在球磨后丧失了其结晶性的至少一部分,甚至可能完全失去其结晶性。一步球磨工艺形成了高度分散的(离子和电子网络),具有使Li2S材料被氧化的增加的三相边界位点,其保持了Li2S正极的离子传导性,有助于电极活性材料利用率和Li2S正极性能的全部改善,并为Li2S正极赋予优异的电化学特性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122826191A_ABST
    Figure CN122826191A_ABST
Patent Text Reader

Abstract

An electrode composite and a method of making the same are disclosed. A mixture comprising lithium sulfide (Li2S) particles containing a Li2S compound, carbon particles, and lithium phosphorus sulfide halide (LPS-X) particles containing a LPS-X (X is F, Cl, Br, and / or I) compound is provided. The LPS-X particles have crystallinity, which can be confirmed by XRD of the LPS-X particles or mixture showing XRD peaks indicative of crystalline LPS-X. The mixture does not include lithium phosphorus sulfide (LPS) particles made from a LPS compound. The mixture is subjected to ball milling to provide a ball-milled composite. At least a portion of the LPS-X compound contained in at least a portion of the LPS-X particles is converted to a LPS compound. XRD of the ball-milled composite does not show XRD peaks indicative of crystalline LPS-X.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-reference to related applications

[0002] This application claims priority to U.S. Patent Application No. 63 / 555,694, filed February 20, 2024, and U.S. Patent Application No. 19 / 051,005, filed February 11, 2025, the disclosures of which are incorporated herein by reference in their entirety. Technical Field

[0003] This disclosure relates to electrode composite materials, electrodes and all-solid-state batteries, and methods for manufacturing electrode composite materials, electrodes and all-solid-state batteries. Background Technology

[0004] Secondary batteries

[0005] Rechargeable batteries have become an increasingly ideal power source for a wide range of electronic devices, including automobiles, computers, mobile phones, tools, scooters, bicycles, electric vehicles, energy storage systems, drones, and other equipment. Among rechargeable batteries, lithium-ion batteries are particularly valued for their ability to provide an ideal balance between voltage and energy density. In addition to their performance advantages, lithium-ion rechargeable batteries contribute to addressing climate change by enabling the electrification of transportation and promoting the integration of renewable energy sources. These batteries help reduce greenhouse gas emissions by powering electric vehicles and storing energy from intermittent renewable energy sources such as solar and wind power. Furthermore, the long cycle life and high energy density of lithium-ion batteries can support the development of smart grids and distributed energy systems, potentially improving overall energy efficiency and reducing dependence on fossil fuels. Traditionally, lithium rechargeable batteries contain liquid electrolytes, which typically contain lithium salts dissolved in organic solvents. However, the development of all-solid-state lithium rechargeable batteries as an alternative to traditional liquid electrolyte systems has received increasing attention. Solid-state batteries offer potential advantages in terms of safety, stability, and energy density. Despite these potential advantages, the development of practical all-solid-state lithium rechargeable batteries still faces several significant challenges.

[0006] Challenges of all-solid-state rechargeable batteries

[0007] One challenge in the design of solid-state batteries is achieving and maintaining sufficient lithium ion diffusivity within solid electrolyte materials. In addition, volume changes (e.g., expansion and contraction) of certain components of the battery, such as electrodes, may occur during charging and discharging of the battery. These volume changes can lead to mechanical stress or cause contact failure between various components within the battery structure. Contact failure between battery components can cause degradation of charge-discharge characteristics as well as degradation of the overall battery capacity. Researchers and engineers in the energy storage field are actively working to address these challenges. Emphasis is placed on the development of new materials and battery designs that can achieve desirable lithium ion diffusivity while also accommodating the mechanical stress associated with battery cycling. Improving the stability of interfaces within solid-state batteries remains an area of research. Overcoming the existing limitations of solid-state battery systems is expected to bring significant progress to energy storage capacity for large-scale applications.

[0008] Lithium-sulfur battery

[0009] Lithium-sulfur batteries, by virtue of their low cost, high theoretical capacity (1675 mAh g -1 and 1166 mAh g -1 ) and expected gravimetric energy density (> 500 Wh kg -1 ), which is required for the paradigm shift of current hard-to-breakthrough technologies such as electric aviation, have the capability to subvert existing lithium-ion battery technologies. Low cost and high abundance make sulfur an excellent material for next-generation energy storage. Despite the promising prospects, the implementation of this technology in the market is hampered by a large number of intrinsic and interfacial challenges, which arise from the conversion effect of the cathode material itself when used with liquid-based electrolytes. These obstacles include: the electronic and ionic insulating properties of Li2S and sulfur, large volume expansion during (de)lithiation, and polysulfide dissolution, wherein soluble redox intermediates (Li2S x , 3<x<8) dissolved in liquid electrolyte trigger the "shuttle effect" that active materials migrate from the cathode to the lithium metal anode, causing irreversible loss of mass and capacity during cycling. The combination of slow reaction kinetics and incompatibility with liquid electrolytes is the main crux that currently limits the large-scale practical application of this technology.

[0010] Cathode architecture for lithium-sulfur batteries

[0011] To realize lithium-sulfur technology in liquid systems, a wide range of material-to-cell-level engineering strategies have been explored. Innovative cathode architectures, by confining sulfur-active materials while providing a porous but highly conductive surface network to ensure sufficient electrochemical reaction sites, have proven effective in addressing volume expansion effects and / or increasing sulfur loading. However, when designed for higher loading, utilization and cycle performance often suffer, heavily relying on heating or electrolyte modification strategies to overcome persistent kinetic limitations. To address this issue, redox mediators are often introduced to modulate the conversion reaction, alter formation kinetics, and reduce overall cell polarization. Various types of materials, such as pseudocapacitive oxides, titanosilicones, and organic polymers, have been studied in elemental sulfur cathodes. Specifically, for Li₂S cathodes, metallocenes, organic electrolytes, or even solid-state electrolytes have been employed to alleviate the significant high activation energy barrier during delithiation. While adding redox mediators helps mitigate undesirable degradation, the additional materials within the cell can affect practicality, thereby reducing the system's energy density. While all these strategies have shown some performance improvements, significant trade-offs still need to be made in terms of cycle life, active material loading, or utilization.

[0012] Solid electrolyte for lithium-sulfur batteries

[0013] Despite numerous studies developing novel cathode architectures, modifying liquid electrolyte chemistry, and introducing redox mediators to mitigate capacity loss, the future of lithium-sulfur chemistry in liquid systems remains uncertain. High-capacity sulfur-based cathodes can overcome the energy density and cost limitations of conventional lithium-ion batteries. However, their development is hampered by the inherent polysulfide dissolution in liquid electrolytes, leading to irreversible capacity loss and poor cycle performance. These challenges primarily stem from the unavoidable instability between liquid electrolytes and polysulfide materials. Replacing liquid electrolytes with compatible solid-state electrolytes (SSEs) could potentially eliminate the polysulfide dissolution problem entirely. The work of Cao et al., using in-situ Raman spectroscopy, confirmed the elimination of the polysulfide "shuttle effect" in an all-solid-state environment, reinforcing the momentum for the shift from liquid to solid electrolytes. Therefore, previous work has explored this option, investigating the feasibility of lithium-sulfur chemistry in various types of SSEs. Sulfide-based electrolytes, due to their high ionic conductivity, excellent mechanical properties, and dry-room compatibility, have become a popular choice and have been primarily explored. These characteristics make sulfide-based electrolytes best suited to meet the requirements and scale-up of lithium-sulfur chemistry. Furthermore, molecular dynamics simulations revealed that sulfide SSEs are the most thermodynamically stable for sulfur cathodes compared to other SSE categories. To date, various sulfide SSEs have been utilized in this research, such as thiophosphate Li3PS4 (LPS), glass-ceramic (Li3PS4-2LiBH4), and most usefully, sulfide-germanium sulfide-type Li6PS5Cl (LPSCl) solid electrolyte. Extensive work has focused on cathode composite engineering, investigating synthetic methods to achieve close cathode / SSE contact to promote reversible electrochemical behavior. Despite the excellent electrochemical and mechanical properties of sulfide SSEs, no practical all-solid-state lithium-sulfur batteries with high utilization, high areal capacity, and good cycle stability have been reported. This is attributed to (chemical)mechanical failures, electrolyte degradation at the carbon interface, and the high tortuosity within the sulfur cathode composite.

[0014] Non-existent technology recognition

[0015] The discussion in this section is intended to provide background information related to the present invention and does not constitute an admission of prior art. Summary of the Invention

[0016] [Technical Issues]

[0017] Composite cathode and all-solid-state battery

[0018] This disclosure provides a highly reversible, high ionic / electronic conductivity cathode made of composite materials, and an all-solid-state battery using this cathode, exhibiting excellent electrochemical performance. Utilizing a sulfide solid electrolyte as the ion conductor, redox mediator, and active material, it achieves ideal cycling performance under high areal capacity and room temperature conditions. The composite cathode provided in this application exhibits high reversibility and achieves up to 10 mAh cm⁻¹ under ambient conditions using a zero-liquid electrolyte. -2 It exhibits high areal capacity and 90% cycle stability after 500 cycles. Furthermore, the micron-sized (<10 μm) cathode particles achieve high utilization without compromising stability.

[0019] One-step grinding method

[0020] This disclosure also provides a scalable one-step milling method for manufacturing the composite cathode material provided in this application. This one-step milling method promotes uniform distribution, induces lithium phosphide sulfide conversion and tight solid-solid contact, thereby improving the electrochemical properties and kinetics of the cathode provided in this application. The improved solid-solid contact can activate the redox activity of the lithium phosphide sulfide (LPS-X) solid electrolyte, enabling it to contribute capacity like an active material and contributing to enhanced cycling stability at high rates. Ball milling also reduces particle size, resulting in a larger surface area.

[0021] [Technical Solution]

[0022] Manufacturing method of electrode composite materials

[0023] One aspect of this disclosure provides a method for manufacturing an electrode composite material. The method includes providing, in a ball milling vessel, a mixture comprising Li2S particles containing a Li2S compound, carbon particles, and LPS-X particles containing a lithium phosphide sulfide (LPS-X) compound, wherein X is selected from the group consisting of F, Cl, Br, I, and combinations thereof, wherein the LPS-X particles are crystalline and can be confirmed by XRD analysis of the LPS-X particles or the mixture showing XRD peaks indicative of crystalline LPS-X, wherein the mixture does not contain LPS particles made from a lithium phosphide sulfide (LPS) compound. The method further includes ball milling the mixture in the ball milling vessel to provide a ball-milled composite material such that at least a portion of the LPS-X compound contained in at least a portion of the LPS-X particles is converted to an LPS compound, and further such that the XRD of the ball-milled composite material does not show XRD peaks indicative of crystalline LPS-X. In some embodiments, the XRD of the ball-milled composite material does not show an XRD peak (211) located at 2θ of 13.7°, which indicates the crystallinity of the LPS compound.

[0024] Solid electrolyte (SSE) particles

[0025] In some embodiments, the ball-milled composite material comprises solid electrolyte (SSE) particles, wherein the SSE particles comprise a first particle containing only the LPS-X compound, a second particle containing only the LPS compound, and a third particle containing both LPS and LPS-X compounds. In some embodiments, the ball-milled composite material comprises solid electrolyte (SSE) particles, wherein at least a portion of the SSE particles contains both LPS and LPS-X compounds.

[0026] The mixture being ball-milled

[0027] In some embodiments, the mixture consists essentially of the Li2S particles, the LPS-X particles, and the carbon particles. In some embodiments, the mixture consists of the Li2S particles, the LPS-X particles, and the carbon particles. In some embodiments, the mixture prior to ball milling comprises: 20% to 40% by weight of Li2S particles based on the total weight of the mixture; and 15% to 20% by weight of carbon particles based on the total weight of the mixture.

[0028] Li2S particles

[0029] In some embodiments, the Li2S particles are ground before ball milling the mixture. In some embodiments, the Li2S particles are ground at 300 to 500 RPM for 10 to 20 hours. In some embodiments, the particle size of the Li2S particles before grinding is 500 nm to 50 μm. In some embodiments, the particle size of the Li2S particles after grinding is 250 nm to 25 μm. In some embodiments, the particle size of the Li2S particles after ball milling the mixture is 100 nm to 1 μm.

[0030] carbon particles

[0031] In some embodiments, the carbon particles comprise one selected from the group consisting of acetylene black (AB) carbon, vapor-grown carbon fiber (VGCF), carbon nanotubes (CNTs), Ketjen black (KB) carbon, and combinations thereof. In some embodiments, the carbon particles have a BET specific surface area of ​​20 m². 2 g -1 Up to 1000 m 2 g -1 In some embodiments, the carbon particles comprise AB carbon. In some embodiments, the BET specific surface area of ​​the carbon particles is 70 m². 2 g -1 .

[0032] Transformation

[0033] In some embodiments, ball milling converts 30% to 70% by weight of LPS-X particles into LPS particles. In some embodiments, ball milling converts 50% by weight of LPS-X particles into LPS particles. In some embodiments, the LPS particles comprise Li3PS4.

[0034] ball milling

[0035] In some embodiments, the mixture is ball-milled at 300 to 550 RPM for 1 minute to 20 hours. In some embodiments, the mixture is ball-milled at 500 RPM for 1 hour.

[0036] Manufacturing methods of electrode composite materials—on the other hand

[0037] Another aspect of this disclosure provides a method for manufacturing another electrode composite material. The method includes providing a mixture in a ball mill container comprising Li2S particles, carbon particles, and LPSCl particles containing a lithium phosphorus sulfide (LPSCl) compound, wherein the LPSCl particles are crystalline, the crystallinity of which can be confirmed by XRD patterns of the LPSCl particles or the mixture exhibiting the following XRD peaks: an XRD peak (111) at 2θ 7.5°, an XRD peak (200) at 2θ 8°, an XRD peak (220) at 2θ 12°, an XRD peak (311) at 2θ 13.5°, and an XRD peak (222) at 2θ 14.5°, wherein the mixture does not contain LPS particles made from a lithium phosphorus sulfide (LPS) compound. The method further includes ball milling the mixture in the ball milling vessel to provide a ball-milled composite material, such that at least a portion of the LPSCl compound contained in at least a portion of the LPSCl particles is converted into an LPS compound, and further such that the XRD of the ball-milled composite material does not show an XRD peak (111) at 2θ 7.5°, an XRD peak (200) at 2θ 8°, an XRD peak (220) at 2θ 12°, an XRD peak (311) at 2θ 13.5°, and an XRD peak (222) at 2θ 14.5°. In some embodiments, the XRD of the ball-milled composite material does not show an XRD peak (211) at 2θ 13.7°, which indicates the crystallinity of the LPS compound.

[0038] Solid electrolyte (SSE) particles

[0039] In some embodiments, the ball-milled composite material comprises solid electrolyte (SSE) particles, wherein the SSE particles comprise a first particle containing only the LPSCl compound, a second particle containing only the LPS compound, and a third particle containing both LPS and LPSCl compounds. In some embodiments, the ball-milled composite material comprises solid electrolyte (SSE) particles, wherein at least a portion of the SSE particles contains both LPS and LPSCl compounds.

[0040] The mixture being ball-milled

[0041] In some embodiments, the mixture consists essentially of the Li₂S particles, the LPSCl particles, and the carbon particles. In some embodiments, the mixture prior to ball milling comprises: 20% to 40% by weight of Li₂S particles based on the total weight of the mixture; and 15% to 20% by weight of carbon particles based on the total weight of the mixture.

[0042] Li2S particles

[0043] In some embodiments, the Li2S particles are ground before ball milling the mixture. In some embodiments, the Li2S particles are ground at 300 to 500 RPM for 10 to 20 hours. In some embodiments, the particle size of the Li2S particles before grinding is 500 nm to 50 μm. In some embodiments, the particle size of the Li2S particles after grinding is 250 nm to 25 μm. In some embodiments, the particle size of the Li2S particles after ball milling the mixture is 100 nm to 1 μm.

[0044] LPSCl particles

[0045] In some embodiments, the LPSCl comprises Li6PS5Cl. In some embodiments, the particle size of the LPSCl particles before ball milling of the mixture is 1 μm to 30 μm.

[0046] carbon particles

[0047] In some embodiments, the carbon particles comprise one selected from the group consisting of acetylene black (AB) carbon, vapor-grown carbon fiber (VGCF), carbon nanotubes (CNTs), Ketjen black (KB) carbon, and combinations thereof. In some embodiments, the carbon particles have a BET specific surface area of ​​20 m². 2 g -1 Up to 1000 m 2 g -1In some embodiments, the carbon particles comprise AB carbon. In some embodiments, the BET specific surface area of ​​the carbon particles is 70 m². 2 g -1 .

[0048] Transformation

[0049] In some embodiments, ball milling converts 30% to 70% by weight of LPSCl particles into LPS particles. In some embodiments, ball milling converts 50% by weight of LPSCl particles into LPS particles. In some embodiments, the LPS particles comprise Li3PS4.

[0050] ball milling

[0051] In some embodiments, the mixture is ball-milled at 300 to 550 RPM for 1 minute to 20 hours. In some embodiments, the mixture is ball-milled at 500 RPM for 1 hour.

[0052] parameter

[0053] In some embodiments, the mixture prior to ball milling comprises: 20% to 40% by weight of Li₂S particles based on the total weight of the mixture, and 15% to 20% by weight of carbon particles based on the total weight of the mixture; wherein the carbon particles comprise one selected from the group consisting of acetylene black carbon, vapor-grown carbon fibers, carbon nanotubes, Ketjen black, and combinations thereof; wherein the LPSCl particles prior to ball milling have a particle size of 1 μm to 30 μm; wherein the Li₂S particles prior to ball milling have a particle size of 250 nm to 25 μm; wherein the ball milling of the mixture is performed at 300 to 550 RPM for 1 hour to 5 hours; and the ball milling converts 30% to 70% by weight of the LPSCl particles into LPS particles.

[0054] Alternative parameters

[0055] In some embodiments, the mixture prior to ball milling comprises: 25% to 35% by weight of Li2S particles based on the total weight of the mixture, and 18% to 20% by weight of carbon particles based on the total weight of the mixture; wherein the carbon particles comprise acetylene black carbon; wherein the ball milling of the mixture is performed at 400 to 500 RPM for 1 to 5 hours; and the ball milling converts 40% to 60% by weight of LPSCl particles into LPS particles.

[0056] Preparation method of electrodes for all-solid-state lithium batteries

[0057] Another aspect of this disclosure provides a method for preparing an electrode for an all-solid-state lithium battery, the method comprising: preparing a ball-milled composite material as provided in this application; and pressing the ball-milled composite material. In some embodiments, the ball-milled composite material is pressed under a pressure of 300 to 500 MPa.

[0058] Manufacturing method of all-solid-state lithium batteries

[0059] Another aspect of this disclosure provides a method for manufacturing an all-solid-state lithium battery, the method comprising: preparing a positive electrode as provided in this application; providing a solid electrolyte layer; and providing a negative electrode such that the solid electrolyte layer is sandwiched between the positive electrode and the negative electrode.

[0060] Electrode composite materials

[0061] Another aspect of this disclosure provides an electrode reactivation material comprising: Li2S particles containing a Li2S compound; carbon particles; and solid electrolyte (SSE) particles, said solid electrolyte (SSE) particles comprising a first particle containing only a lithium phosphine sulfide (LPS-X) compound, a second particle containing only a lithium phosphine sulfide (LPS) compound, and a third particle containing both LPS and LPS-X compounds, wherein X is selected from the group consisting of F, Cl, Br, I, and combinations thereof, wherein the XRD of the electrode composite material does not show an XRD peak indicating crystallization of LPS-X. In some embodiments, the XRD of the electrode composite material does not show an XRD peak (211) located at 2θ of 13.7°, which indicates the crystallinity of the LPS compound. An example electrode composite material comprises: Li2S particles containing a Li2S compound; carbon particles; and solid electrolyte (SSE) particles, said solid electrolyte (SSE) particles comprising a first particle containing only a lithium phosphorus sulfide chloride (LPSCl) compound, a second particle containing only a lithium phosphorus sulfide (LPS) compound, and a third particle containing both LPS and LPSCl compounds. The XRD pattern of the electrode composite material does not show the following XRD peaks indicating crystalline LPSCl: (111) at 2θ 7.5°, (200) at 2θ 8°, (220) at 2θ 12°, (311) at 2θ 13.5°, and (222) at 2θ 14.5°. In some embodiments, the XRD pattern of the electrode composite material does not show the XRD peak (211) at 2θ 13.7°, which indicates the crystallinity of the LPS compound.

[0062] Composition of electrode composite materials

[0063] In some embodiments, the electrode composite material provided in this application comprises: 20% to 40% by weight of Li₂S particles based on the total weight of the electrode composite material; and 15% to 20% by weight of carbon particles based on the total weight of the electrode composite material. In some embodiments, the Li₂S particles have a particle size of 100 nm to 1 μm. In some embodiments, the carbon particles comprise one selected from the group consisting of acetylene black (AB) carbon, vapor-grown carbon fiber (VGCF), carbon nanotubes (CNTs), Ketjen black (KB) carbon, and combinations thereof.

[0064] electrode

[0065] Another aspect of this disclosure provides an electrode comprising the electrode reactivation material provided in this application.

[0066] All-solid-state batteries

[0067] Another aspect of this disclosure provides an all-solid-state battery comprising: a positive electrode containing the electrode composite material provided in this application; a negative electrode; and a solid electrolyte layer disposed between the positive electrode and the negative electrode and configured to enable the transport of lithium ions between the positive electrode and the negative electrode.

[0068] Summary rather than limitation

[0069] It should be understood that the invention is not limited to the examples summarized in this summary description. Various other aspects are also described and illustrated in this application.

[0070] [Beneficial Effects]

[0071] One-step ball milling improves the performance of Li2S cathode

[0072] Li₂S active materials exhibit a high activation energy barrier when oxidized to sulfur. According to this disclosure, Li₂S, LPS-X (such as LPSCl), and carbon are ball-milled together to activate Li₂S. It has been found that ball milling not only activates Li₂S but also causes LPS-X (such as LPSCl) to lose its crystal peaks in XRD analysis after ball milling, which is unexpected and surprising. XRD data show that LPSCl loses at least a portion of its crystallinity after ball milling, and may even lose its crystallinity completely. The one-step ball milling process forms a highly dispersed (ionic and electron network) with increased three-phase boundary sites for the oxidation of Li₂S materials, which maintains the ionic conductivity of the Li₂S cathode, contributing to the overall improvement of electrode active material utilization and Li₂S cathode performance, and endowing the Li₂S cathode with excellent electrochemical properties. Attached Figure Description

[0073] Figure 1A The particle distribution of an example ball-milled composite material according to an embodiment of the present disclosure is shown.

[0074] Figure 1B It shows Figure 1A Example three-phase boundary of particles in the image.

[0075] Figure 1C The particle distribution of the hand-mixed material is shown.

[0076] Figure 1D The particle distribution of the material in the two-step ball milling process is shown.

[0077] Figure 2 This is an example of a solid-state battery according to an embodiment of the present disclosure.

[0078] Figure 3A This is a SEM image of the obtained Li2S particles.

[0079] Figure 3B This is an SEM image of ground LPSCl particles.

[0080] Figure 3C This is a SEM image of AB carbon.

[0081] Figure 3D It is the original Li2S material in combination with Figure 3A SEM images at different magnifications.

[0082] Figure 3E This is an SEM image of the ground Li2S material.

[0083] Figure 4 This is a diagram of a ball mill according to some embodiments of this disclosure.

[0084] Figure 5 The XRD results of the ground Li2S / LPSCl / C mixture, the ground Li2S / LPSCl mixture, LPSCl, and Li2S are shown.

[0085] Figures 6A to 6F Synchrotron radiation XAS results of the composite material prepared in Example 1-1 are shown. Figure 6A For reference spectrum, Figures 6B to 6D XAS of the original, charged, and discharged composite materials are shown. Figure 6E This is the original spectrum of the SK edge. Figure 6F The results of the linear combination fitting are shown.

[0086] Figure 7 This is a diagram illustrating the manufacture of an all-solid-state battery according to an embodiment of the present disclosure.

[0087] Figure 8 The specific capacity of the batteries in Examples 5-4 is shown.

[0088] Figure 9 The specific capacity of the batteries in Examples 5-5 is shown.

[0089] Figure 10 The specific capacity measured for the batteries in Examples 5-6 is shown.

[0090] Figure 11 A comparison of the specific capacity of the batteries in Examples 6-4, 6-5, and 6-6 is shown.

[0091] Figure 12 The specific capacity of the batteries manufactured in Examples 7-3 is shown as measured during repeated cycling.

[0092] Figure 13 The specific capacity of the batteries manufactured in Examples 7-4 is shown.

[0093] Figure 14 The specific capacity of the cells with 30, 35, and 40% by weight of Li2S is shown.

[0094] Figure 15 The specific capacity of the cells with 50, 60, and 70% by weight of Li2S is shown.

[0095] Examples, not limitations

[0096] The examples set forth in this application illustrate specific non-limiting implementations in one form, and such examples should not be construed as limiting the scope of the appended claims in any way. Detailed Implementation

[0097] Examples and Implementation

[0098] The subject matter of this disclosure will now be described and discussed in more detail with reference to the accompanying drawings, which illustrate some, but not all, of the embodiments of the invention, as well as some specific embodiments and examples. Unless otherwise stated, the same reference numerals always refer to the same elements or parts. The subject matter of this disclosure can be embodied in many different forms and should not be construed as being limited to the specific embodiments set forth in this application. Rather, these embodiments are provided to enable this disclosure to meet the requirements of applicable law. In fact, many modifications and other embodiments of the subject matter of this disclosure will arise in the mind of one skilled in the art to which the subject matter of this disclosure pertains. Therefore, it should be understood that the subject matter of this disclosure is not limited to the specific embodiments disclosed, and that modifications and other embodiments are intended to be included within the scope of the appended claims.

[0099] definition

[0100] “one,” “a kind,” and “the”

[0101] Unless the context clearly indicates otherwise, the singular form of the words used in this application also includes the plural form. The plural encompasses the singular, and vice versa. Therefore, references to "an," "a," and "the" generally include the plural form of the corresponding term. For example, although this disclosure describes layers, substrates, and units, etc., in the singular form, more than one of these and other components, including combinations, may also be used.

[0102] "about"

[0103] The term “about” indicates and covers a specified numerical value and the range above and below that value.

[0104] "Contains", "Basically consists of", and "Composed of"

[0105] The terms “comprising” and “containing” should be interpreted inclusively rather than exclusively. Similarly, the terms “including” and “or” should be interpreted inclusively unless the context explicitly prohibits such an interpretation. Disclosure of embodiments defined using the term “comprising” is also a disclosure of embodiments “substantially constitute” and “compose” of the disclosed ingredients. The phrase “composes of” excludes any element, step, or ingredient not expressly specified.

[0106] "and / or"

[0107] The term “and / or” used in the context of “X and / or Y” should be interpreted as “X”, “Y”, or “X and Y”.

[0108] "Up" and "above"

[0109] As used in this application, the terms “on,” “applied to,” “formed on,” “deposited on,” “set on,” etc., mean to apply, form, cover, deposit, or set on a surface that is below or above it. Conversely, the terms “above,” “applied above,” “formed above,” “deposited above,” “covered above,” “set above,” etc., mean to apply, form, cover, deposit, or set on or above it, but not necessarily in contact with a surface. For example, a forming layer “applied above” a substrate layer may contact the substrate without intermediate material; however, this expression does not preclude the presence of one or more other layers of the same or different composition located between the forming layer and the substrate layer.

[0110] Markush Group

[0111] As used in any Markush-type representation, the term "combination thereof" means a combination of one or more elements selected from a group of elements disclosed in the Markush-type representation, and refers to the presence of one or more elements selected from that group. The term "combination thereof" includes every possible combination of the elements referred to by the term.

[0112] "between"

[0113] The term "between" as used in this application includes endpoints.

[0114] Numerical range

[0115] Furthermore, all numerical ranges in this application should be understood to include all integers, natural numbers, or fractions within that range. Moreover, any numerical range referred to in this application is intended to include all subranges it covers, and these numerical ranges should be interpreted as supporting claims relating to any numerical value or subset of numerical values ​​within that range. For example, the disclosure of 1 to 10 should be interpreted as supporting ranges such as 1 to 8, 3 to 7, 1 to 9, 3.6 to 4.6, 3.5 to 9.9, etc. When ranges are given, any endpoints of these ranges and / or numbers within these ranges may be combined with the ranges of this disclosure.

[0116] "Including", "such as", and "for example"

[0117] As used in this application, the terms “including,” “such as,” “for example,” etc., mean “including / such as / for example but not limited to.”

[0118] Combination of implementation methods

[0119] The term "example" as used in this application, especially when followed by a series of terms, is illustrative only and should not be considered exclusive or exhaustive. Unless otherwise expressly stated, any embodiment disclosed in this application may be combined with any other embodiment disclosed in this application.

[0120] Particle size

[0121] The particle size used in this application refers to the average particle size (D) measured using a microscope (e.g., optical microscope, electron microscope, scanning electron microscope (SEM), transmission electron microscope (TEM), atomic force microscope (AFM), confocal microscope, X-ray microscope, cryo-electron microscope, Raman microscope, or fluorescence microscope). 50 The particle size can be the diameter of a spherical particle, or the length along the direction of its maximum size for an ellipsoidal or other irregularly shaped particle. The particle size used in this application has a "D" value. 50 This refers to the diameter of 50% of the particles being smaller than this value.

[0122] Lithium sulfide cathode

[0123] Electron and ionic insulation of Li2S

[0124] Lithium sulfide (Li₂S) is a key material used in lithium-sulfur batteries, particularly as the cathode. However, Li₂S has a wide band gap (approximately 3.6 eV), making it a strong electronic insulator. This wide band gap restricts the movement of electrons at ambient temperatures, hindering significant electrical conduction. Furthermore, while Li₂S suppresses electron flow, it allows the transport of lithium ions (Li), which is crucial for its performance in battery applications. However, its ionic conductivity is relatively low compared to other solid-state materials.

[0125] Volume change

[0126] Volume changes in lithium-sulfur batteries are a key challenge affecting both battery performance and durability. This effect stems from the significant volume changes that occur during the interconversion of Li₂S and sulfur during charging and discharging. During charging, Li₂S reverts to sulfur, causing volume shrinkage. Conversely, during discharging, sulfur reacts with lithium ions to form Li₂S, resulting in considerable volume expansion—sulfur can increase its volume by up to 80%.

[0127] Mechanical strain

[0128] Cyclic expansion and contraction subject battery components to repeated stress. The dramatic volume change between sulfur and Li₂S causes mechanical strain on the cathode. Over time, this stress can cause the electrode material to crack or break, leading to the loss of active sulfur and capacity decay. Mechanical strain can also cause sulfur to separate from the conductive network, further degrading the overall battery performance.

[0129] Instability of positive electrode structure

[0130] Furthermore, repeated volume changes introduce instabilities into the cathode structure, disrupting the necessary pathways for electron and lithium-ion flow. Disruption of conductive channels reduces battery efficiency and shortens its lifespan. Therefore, volume changes in lithium-sulfur batteries are a significant obstacle to long-term performance, as the continuous expansion and contraction of sulfur / Li2S leads to structural damage and efficiency loss.

[0131] Polysulfide dissolution

[0132] Polysulfide dissolution is a major problem in lithium-sulfur batteries, negatively impacting battery performance and lifespan. This primarily stems from the incompatibility between the liquid electrolyte and the polysulfide materials, specifically the dissolution of sulfur compounds into the electrolyte during battery operation. Specifically, during discharge, sulfur (S8) is reduced to form long-chain polysulfides (Li2S8, Li2S6, etc.), which are soluble in most liquid electrolytes used in lithium-sulfur batteries. These dissolved polysulfides can migrate between the negative and positive electrodes. Over time, they are further reduced to short-chain polysulfides (Li2S4, Li2S2, Li2S) or completely converted into solid lithium sulfide (Li2S).

[0133] Irreversible mass and capacity loss

[0134] However, this polysulfide migration causes some of these sulfur compounds to shuttle to the lithium anode, where they can be reduced and reoxidized during repeated cycles, resulting in the so-called "shuttle effect." This process leads to irreversible mass and capacity losses during cycling. The polysulfides that dissolve and migrate from the cathode can no longer participate in electrochemical reactions, causing a gradual loss of active sulfur and a decrease in battery capacity.

[0135] Undesirable side effects

[0136] Furthermore, polysulfides reaching the negative electrode can react with lithium metal, forming a passivation layer and consuming lithium in undesirable side reactions. This reduces lithium-ion availability and lowers the overall battery efficiency. In addition, the continuous movement of polysulfides between electrodes leads to poor coulombic efficiency and limits the number of charge-discharge cycles the battery can perform before performance deteriorates.

[0137] Electrolyte degradation at carbon interface

[0138] In lithium-sulfur batteries, carbon materials are often used to improve the conductivity of sulfur and Li₂S because sulfur and Li₂S are non-conductive. However, during battery operation, especially under high voltage and cycling conditions, the electrolyte can decompose at the carbon interface. This degradation is particularly pronounced when polysulfides formed during charge and discharge come into contact with carbon materials. The reactivity of these intermediate sulfur species can accelerate electrolyte decomposition. This electrolyte degradation poses a significant challenge to maintaining battery performance and lifespan.

[0139] Insulation byproducts

[0140] Furthermore, the decomposition of the electrolyte on the surface of carbon materials can lead to the formation of insulating byproducts, such as solid layers accumulating at the interface. These byproducts, often composed of lithium salts or other reaction residues, can block ion pathways and reduce lithium-ion transport efficiency. As a result, the active surface area of ​​carbon is reduced, limiting the overall battery capacity and decreasing the ability of sulfur to react effectively during cycling.

[0141] conductivity loss

[0142] Furthermore, electrolyte degradation can also damage the conductive network established by the carbon matrix. Over time, as the electrolyte decomposes and forms an insulating layer, the bond between sulfur and carbon weakens. This loss of conductivity leads to increased internal resistance in the battery, negatively impacting both power output and energy efficiency, making it less suitable for high-performance applications. Additionally, as the electrolyte continues to degrade at the carbon interface, the battery's long-term stability is compromised. With each charge-discharge cycle, the accumulation of degradation products and the weakening of the conductive network result in rapid capacity decay and shortened battery life.

[0143] High tortuosity

[0144] The high tortuosity of the Li₂S cathode in lithium-sulfur batteries significantly hinders their performance. Tortuosity refers to the complex and winding path that ions must traverse through the porous structure of the cathode. In the case of lithium-sulfur batteries, high tortuosity severely restricts the efficient movement of lithium ions and electrons, leading to a variety of performance-related problems.

[0145] Slowed ion transport

[0146] In lithium-sulfur batteries, lithium ions need to move efficiently across the Li₂S cathode during charge-discharge cycles. When the internal structure of the cathode is highly tortuous, these ions must migrate along long and winding paths. This increased diffusion distance slows down ion transport, resulting in sluggish charge-discharge kinetics and poor power output.

[0147] Increased internal resistance

[0148] Furthermore, the difficulty of transporting ions and electrons through the highly tortuous structure leads to increased internal resistance. As electrons and ions require longer paths to complete the reaction, the battery experiences higher polarization. This means more energy is needed to drive the electrochemical processes, resulting in reduced efficiency and lower energy output during operation.

[0149] Uneven strain and degradation

[0150] High tortuosity can also lead to uneven strain and degradation in the cathode material. Due to the uneven utilization of the cathode active material, specific areas of the cathode are subjected to higher stress, which can lead to mechanical failure, cracking, and loss of material integrity over time. As these areas deteriorate, the overall performance of the battery decreases, shortening its cycle life and limiting the number of effective charge-discharge cycles it can perform.

[0151] Manufacturing electrode composite materials

[0152] One aspect of this disclosure provides a method for manufacturing an electrode composite material, wherein a mixture comprising Li₂S particles, carbon particles, and LPSCl particles containing a lithium phosphorus sulfide (LPSCl) compound is provided in a ball milling vessel. The LPSCl particles are crystalline, as can be confirmed by XRD patterns of the LPSCl particles or the mixture exhibiting the following XRD peaks: an XRD peak (111) at approximately 2θ 7.5°, an XRD peak (200) at approximately 2θ 8°, an XRD peak (220) at approximately 2θ 12°, an XRD peak (311) at approximately 2θ 13.5°, and an XRD peak (222) at approximately 2θ 14.5°. The mixture does not contain LPS particles made from a lithium phosphorus sulfide (LPS) compound. The mixture is then ball-milled in a ball milling vessel to provide a ball-milled composite material. At least a portion of the LPSCl compound contained in at least a portion of the LPSCl particles is converted to an LPS compound.

[0153] lithium, phosphorus, sulfur, and chlorine

[0154] LPSCl (Li6PS5Cl) is renowned for its high ionic conductivity, a key characteristic of solid electrolyte materials. High ionic conductivity allows lithium ions to move efficiently within the material, thus facilitating the charge-discharge process in solid-state batteries. LPSCl also exhibits good chemical and thermal stability, which is important for the long-term performance and safety of solid-state batteries. Stability is particularly critical in high-temperature and high-voltage applications. Furthermore, LPSCl possesses a wide electrochemical stability window, capable of withstanding a wide voltage range without undergoing undesirable reactions. This is essential for supporting a variety of cathode and anode materials.

[0155] Mixture before ball milling

[0156] In some embodiments, the mixture prior to ball milling may consist essentially of the Li₂S particles, the LPSCl particles, and the carbon particles.

[0157] Solid electrolyte particles in ball-milled composite materials

[0158] The ball-milled composite material comprises solid electrolyte (SE) particles, wherein the SE particles comprise a first particle containing only the LPSCl compound, a second particle containing only the LPS compound, and a third particle containing both LPS and LPSCl compounds. In some embodiments, the ball-milled composite material comprises solid electrolyte (SE) particles, wherein at least a portion of the SE particles contains both LPS and LPSCl compounds.

[0159] Loss of crystallinity of LPSCl

[0160] The XRD patterns of the ball-milled composite material did not show any XRD peaks indicating the crystallinity of LPSCl, namely (111) at approximately 7.5°, (200) at approximately 8°, (220) at approximately 12°, (311) at approximately 13.5°, and (222) at approximately 14.5°. This indicates that LPSCl was transformed or decomposed into other substances during ball milling, and therefore at least some or all of the crystallinity of LPSCl was lost after ball milling.

[0161] Other stoichiometric ratios in LPS-X and / or substitutions such as F, I, and Br can be used instead of using Cl alone. Using these substituted halogen elements can improve ionic conductivity or alter electrochemical stability, thereby improving the electrochemical performance of the system.

[0162] Therefore, another aspect of this disclosure provides a method for manufacturing an electrode composite material. Specifically, in a ball milling vessel, a mixture comprising Li2S particles containing a lithium sulfide (Li2S) compound, carbon particles, and LPS-X particles containing a lithium phosphide sulfide (LPS-X) compound is provided. X is selected from the group consisting of F, Cl, Br, I, and combinations thereof. The LPS-X particles are crystalline and can be confirmed by XRD analysis of the LPS-X particles or the mixture showing XRD peaks indicating crystalline LPS-X. The mixture does not contain LPS particles made from a lithium phosphide sulfide (LPS) compound. The mixture is ball-milled in a ball milling vessel to provide a ball-milled composite material. At least a portion of the LPS-X compound contained in at least a portion of the LPS-X particles is converted into an LPS compound.

[0163] Mixture before ball milling

[0164] The mixture prior to ball milling may consist essentially of the Li2S particles, the LPS-X particles, and the carbon particles.

[0165] LPS-X particles

[0166] LPS-X granules may contain LPSF. LPS-X granules may contain LPSCl. LPS-X granules may contain LPSBr. LPS-X granules may contain LPSI. LPS-X granules may contain any two or more of LPSF, LPSCl, LPSBr, and LPSI. LPS-X granules may contain LPSF and LPSCl. LPS-X granules may contain LPSF and LPSBr. LPS-X granules may contain LPSF and LPSI. LPS-X granules may contain LPSCl and LPSBr. LPS-X granules may contain LPSCl and LPSI. LPS-X granules may contain LPSF, LPSCl, and LPSBr. LPS-X granules may contain LPSF, LPSCl, and LPSI. LPS-X granules may contain LPSF, LPSCl, LPSBr, and LPSI. LPS-X granules may contain LPSF, LPSCl, LPSBr, and LPSI.

[0167] Loss of crystallinity of LPS-X

[0168] The XRD pattern of the ball-milled composite material did not show XRD peaks indicating crystalline LPS-X. This indicates that LPS-X was transformed or decomposed into other substances during the ball milling process, and therefore at least some or all of the crystallinity of LPSCl was lost after ball milling.

[0169] Solid electrolyte particles in ball-milled composite materials

[0170] The ball-milled composite material comprises solid electrolyte (SE) particles, wherein the SE particles comprise a first particle containing only the LPS-X compound, a second particle containing only the LPS compound, and a third particle containing both LPS and LPS-X compounds. In some embodiments, the ball-milled composite material comprises solid electrolyte (SE) particles, wherein at least a portion of the SE particles contains both LPS and LPS-X compounds.

[0171] Poor crystallinity or nanocrystallinity of LPS

[0172] In all aspects provided in this application, the XRD of the ball-milled composite material does not show an XRD peak (211) located at approximately 13.7° 2θ, which indicates the crystallinity of the LPS compound. This suggests that the LPS in the ball-milled composite material has low or nanocrystalline properties.

[0173] Grinding Li2S particles

[0174] Li2S particles can be pre-ground before being provided to form a mixture to be ball-milled. The grinding of Li2S particles can be one or more of the following: ball milling, jet milling, stirred (stirring media) milling, hammer milling, roller milling, planetary milling, ultrasonic milling, colloid milling, pin milling, and / or any other suitable grinding process. It should be noted that the methods provided in this application are also applicable to "as is" Li2S. Reducing the particle size can increase the overall cell capacity and improve performance.

[0175] Li2S particle grinding speed

[0176] The grinding of Li2S particles can be performed at a speed of approximately 300 to 500 RPM, for example at 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, or 500 RPM or around thereon. In an embodiment, the grinding speed of the Li2S particles can be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​within the range of approximately 300 RPM to approximately 500 RPM.

[0177] Li2S particle grinding time

[0178] The grinding of Li2S particles can be carried out for approximately 10 to 20 hours, for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20 hours or about. In an embodiment, the ball milling can be carried out for a period of time within the range formed by selecting any two values ​​listed above or by selecting any two values ​​within the range of approximately 10 hours to approximately 20 hours.

[0179] Li2S particle size before grinding

[0180] The particle size of the Li₂S particles before grinding can be from about 500 nm to about 50 μm. In embodiments, the average particle size of the Li₂S particles before grinding can be any value or around 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50 μm. In embodiments, the Li₂S particle size can be within a range formed by selecting any two values ​​listed above or any two values ​​in the range of about 500 nm to about 50 μm.

[0181] Particle size of Li2S after grinding

[0182] The particle size of the Li₂S particles after grinding but before ball milling in the mixture can be from about 250 nm to about 25 μm. In embodiments, the average particle size of the Li₂S particles after grinding but before ball milling in the mixture can be any value or around 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, or 25 μm. In embodiments, this Li₂S particle size can be within a range formed by selecting any two values ​​listed above or selecting any two values ​​in the range of about 250 nm to about 25 μm.

[0183] Li2S particle size in ball-milled composite materials

[0184] The particle size of the Li₂S particles after ball milling in the ball-milled composite material can be from about 100 nm to about 1 μm. In embodiments, the average particle size of the Li₂S particles after ball milling in the ball-milled composite material can be any value or around 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1 μm. In embodiments, this Li₂S particle size can be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​in the range of about 100 nm to about 1 μm.

[0185] Carbon particle type

[0186] The carbon particles may comprise one or more types, such as Super P carbon black, Ketjen black carbon, acetylene black carbon, natural graphite, artificial graphite, expanded graphite, single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), graphene, graphene oxide (GO), reduced graphene oxide (rGO), carbon nanofibers (CNFs), carbon nano-onions, mesoporous carbon, carbon quantum dots (CQDs), carbon aerogels, or bio-derived carbon particles. For example, the carbon particles may comprise one selected from the group consisting of acetylene black (AB) carbon, vapor-grown carbon fibers (VGCF), carbon nanotubes (CNTs), Ketjen black (KB) carbon, and combinations thereof. In some embodiments, the carbon particles may comprise AB carbon.

[0187] carbon particle surface area

[0188] The BET specific surface area of ​​carbon particles can be approximately 20 m². 2 g -1 Approximately 1000 m 2 g-1 Within the range, for example: 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, 500, 510 520, 530, 540, 550, 560, 570, 580, 590, 600, 610, 620, 630, 640, 650, 660, 670, 680, 690, 700, 710, 720, 730, 740, 750, 760, 770, 780, 790, 800, 810, 820, 830, 840, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950, 960, 970, 980, 990 or 1000 m 2 g -1 Or approximately. In an embodiment, the BET specific surface area of ​​the carbon particles can be determined by selecting any two values ​​listed above or selecting approximately 20 m². 2 g -1 Approximately 1000 m 2 g -1 The range formed by any two values ​​within the range. For example, in some embodiments, the BET specific surface area of ​​carbon particles can be approximately 70 m². 2 g -1 .

[0189] Conversion rate

[0190] Ball milling can convert approximately 30% to approximately 70% by weight of LPSCl compound into LPS compound. For example, the weight percentage of LPSCl compound converted into LPS compound can be 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, or 70% by weight or approximately thereafter. In embodiments, the weight percentage of LPSCl compound converted into LPS compound can be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​within the range of approximately 30% to approximately 70% by weight. For example, in some embodiments, ball milling can convert approximately 50% by weight of LPSCl particles into LPS particles.

[0191] The LPS particles may contain Li3PS4.

[0192] Li2S particle weight percentage

[0193] The mixture prior to ball milling may contain approximately 20% to approximately 40% by weight of Li₂S particles based on the total weight of the mixture. For example, the weight percentage of Li₂S particles based on the total weight of the mixture may be 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, or 40% by weight or approximately thereafter. In embodiments, the weight percentage of Li₂S particles based on the total weight of the mixture may be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​within the range of approximately 20% to approximately 40% by weight.

[0194] carbon particle weight percentage

[0195] The mixture prior to ball milling may contain approximately 15% to approximately 20% carbon particles based on the total weight of the mixture. For example, the weight percentage of carbon particles may be 15, 16, 17, 18, 19, or 20% by weight, or about, based on the total weight of the mixture. In embodiments, the weight percentage of carbon particles based on the total weight of the mixture may be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​within the range of approximately 15% to approximately 20% by weight.

[0196] LPS-X particle size

[0197] The volume-based average particle size of LPS-X particles, as measured by laser diffraction-based particle size distribution measurement, can be, for example, about 0.1 μm to about 50 μm, about 0.1 μm to about 40 μm, about 0.1 μm to about 30 μm, about 0.1 μm to about 20 μm, about 0.1 μm to about 10 μm, about 0.1 μm to about 5 μm, about 0.1 μm to about 1 μm, about 1 μm to about 50 μm, about 1 μm to about 40 μm, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 1 μm to about 10 μm, about 1 μm to about 5 μm, about 5 μm to about 50 μm. Approximately 5μm to approximately 40μm, approximately 5μm to approximately 30μm, approximately 5μm to approximately 20μm, approximately 5μm to approximately 10μm, approximately 10μm to approximately 50μm, approximately 10μm to approximately 40μm, approximately 10μm to approximately 30μm, approximately 10μm to approximately 20μm, approximately 20μm to approximately 50μm, approximately 20μm to approximately 40μm, approximately 20μm to approximately 30μm, approximately 20μm to approximately 50μm, approximately 20μm to approximately 40μm, approximately 20μm to approximately 30μm, approximately 30μm to approximately 50μm, approximately 30μm to approximately 40μm, approximately 40μm to approximately 50μm, etc. In embodiments, the average particle size of LPS-X particles can be in the range of about 0.1 μm to about 50 μm, for example, any value of about 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50 μm. In embodiments, the LPS-X particle size can be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​in the range of about 0.1 μm to about 50 μm.

[0198] ball milling

[0199] Ball Mill Overview

[0200] Ball milling is an important technology for mixing and preparing materials for solid-state batteries. It is a widely used mechanical technique for grinding powders into fine particles and mixing materials in various applications, including the preparation of solid-state battery components. In the case of solid-state batteries, ball milling is often used to mix and blend electrode materials, solid electrolytes, and other components. Exemplary ball milling apparatuses may include planetary ball mills, stirred ball mills, and vibratory ball mills. These apparatuses typically consist of a rotating or vibrating chamber containing grinding balls made of materials such as steel, ceramic, or zirconium oxide.

[0201] homogeneous mixing

[0202] Ball milling can effectively achieve homogeneous mixtures of different powders. This is crucial for ensuring the uniform distribution of components in electrode materials and solid electrolytes, which in turn affects the overall performance of the battery.

[0203] Reduce particle size

[0204] Ball milling reduces the particle size of related materials, leading to increased surface area and improved reactivity. Here, ball milling of the mixture reduces the particle size within the mixture, resulting in a larger surface area compared to the mixture before ball milling. Smaller particle sizes can enhance the kinetics of electrochemical reactions, contributing to better battery performance. The micron-sized particles (<10 μm) in the composite material provided in this application achieve high utilization without compromising stability.

[0205] Enhanced electrode-electrolyte interface

[0206] Ball milling can help form a well-defined interface between the electrode and the solid electrolyte. This is important for promoting efficient ion transport and minimizing interfacial resistance within solid-state batteries.

[0207] Promote solid-state reaction

[0208] Ball milling can induce solid-state reactions between different components, promoting the formation of desired phases and structures in the material. This is particularly relevant for the synthesis of composite electrode materials or the preparation of the composite electrolyte materials provided in this application. Here, ball milling provides the energy to convert or decompose LPS-X into LPS.

[0209] shorten lithium-ion diffusion length

[0210] Here, after ball milling of the mixture, compared with the situation between Li2S particles and LPS-X particles before ball milling, the Li2S particles and SSE particles in the ball-milled composite material are in closer contact. Compared with the un-ball-milled mixture, this closer contact shortens the lithium-ion diffusion length in the electrode composite material.

[0211] Optimize conductivity

[0212] Ball milling can be used to optimize the conductivity of electrode materials by ensuring good distribution of conductive additives (such as carbon or metal nanoparticles) in the composite or in the solid electrolyte provided in this application.

[0213] Controlling morphology

[0214] The grinding process can also affect the morphology of the material, including particle shape, size, and distribution. Controlling these aspects is important for achieving the desired electrochemical properties and the overall performance of solid-state batteries.

[0215] Three-phase boundary site

[0216] Here, due to the formation of LPS in the ball-milled composite material, ball milling increases the three-phase boundary sites between Li2S particles, residual LPS-X particles, and newly formed LPS particles or particles containing newly formed LPS at the surface of Li2S particles in the mixture, which oxidizes Li2S to sulfur, thus facilitating enhanced lithium-ion transport in the electrode composite material. For example... Figure 1A As shown, in an example ball-milled composite containing Li2S, LPS, LPSCl, and carbon particles, a one-step ball milling process achieved an excellent distribution of Li2S, LPS, and LPSCl ion particles, forming a composite architecture with sufficient three-phase boundary contact points to facilitate good ion and electron transport and effective (de)lithiation. Figure 1B As shown, these ionic particles form the three-phase boundaries where they contact each other, with carbon particles distributed at these three-phase boundaries in contact with each of the particles. Conductive carbon particles form a conductive carbon network throughout the ball-milled composite material, providing conductivity and facilitating lithium-ion transport throughout the material. Furthermore, LPS, being the most stable electrolyte with α-sulfur, forms an interfacial two-dimensional channel that lowers the activation barrier for lithium diffusion; the high oxidation tendency of LPSCl can then help overcome the slow kinetics of Li₂S charging to sulfur.

[0217] Comparing one-step ball milling and hand mixing

[0218] In comparison, such as Figure 1C As shown, in the example composite material prepared by manually mixing Li2S, LPSCl, and carbon particles, no LPS was formed, and the Li2S, LPSCl, and carbon particles did not react as expected. Figure 1A Such a uniform distribution. These particles themselves form isolated regions of Li2S, LPSCl, and carbon particles, resulting in a poorer ionic and electron network in the mixture compared to the composite material prepared by one-step ball milling in the method provided in this application, and a lower active surface area. Manual mixing has low energy, insufficient to promote the conversion of LPSCl to LPS.

[0219] Comparison of one-step ball milling and two-step ball milling

[0220] On the other hand, although two-step ball milling can achieve similar energies to one-step ball milling, it also forms Li₂S clusters and isolated regions of carbon particles surrounding these clusters. Therefore, two-step ball milling also results in a poorer ionic and electron network in the obtained material, and a lower active surface area.

[0221] Improved solid-solid contact

[0222] One-step ball milling promotes uniform distribution, induces sulfur amorphization and a tight cathode / SSE solid-solid contact, resulting in enhanced electrochemical properties and kinetics of the composite material, providing a cathode composite with reversible and high ionic / electronic conductivity. The improved solid-solid contact activates the redox activity of the sulfide-germanium sulfide-type LPSCl electrolyte, contributing capacity like an active material, and enabling practical all-solid-state lithium-sulfur batteries with high utilization, areal capacity and good cycle stability.

[0223] Energy considerations

[0224] Ball milling is an energy-intensive process that requires careful control of the milling time and speed to avoid overheating that could lead to unwanted reactions or material damage.

[0225] ball mill speed

[0226] The ball milling of the mixture can be performed at speeds of approximately 300 to approximately 550 RPM, for example at 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, 500, 510, 520, 530, 540, or 550 RPM or around thereon. In embodiments, the ball milling speed of the mixture can be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​within the range of approximately 300 RPM to approximately 550 RPM. For example, in some embodiments, the ball milling of the mixture can be performed at approximately 500 RPM.

[0227] Ball grinding time

[0228] The ball milling of the mixture can be carried out for approximately 1 minute to approximately 20 hours, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59 minutes, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 hours or approximately. In implementations, ball milling can be performed for a time range formed by selecting any two values ​​listed above or by selecting any two values ​​within the range of approximately 1 minute to approximately 20 hours. For example, in some implementations, the mixture may be ball-milled for approximately 1 hour.

[0229] Ball milling conditions - examples

[0230] In some embodiments, the mixture prior to ball milling comprises: Li2S particles in an amount of about 20% to about 40% by weight based on the total weight of the mixture, and carbon particles in an amount of about 15% to about 20% by weight based on the total weight of the mixture; the carbon particles comprise one selected from the group consisting of acetylene black carbon, VGCF, CNT, Ketjen black, and combinations thereof; the LPS-X particles prior to ball milling have a particle size of about 1 μm to about 30 μm; the Li2S particles prior to ball milling have a particle size of about 250 nm to about 25 μm; the ball milling of the mixture is performed at about 300 to about 550 RPM for about 1 hour to about 5 hours; and the ball milling converts about 30% to about 70% by weight of the LPS-X particles into LPS particles.

[0231] Ball milling conditions – another example

[0232] For example, when LPS-X contains LPSCl, the mixture prior to ball milling comprises: approximately 20% to approximately 40% by weight of Li2S particles based on the total weight of the mixture, and approximately 15% to approximately 20% by weight of carbon particles based on the total weight of the mixture; the carbon particles comprise one selected from the group consisting of acetylene black carbon, VGCF, CNT, Ketjen black, and combinations thereof; the LPSCl particles prior to ball milling have a particle size of approximately 1 μm to approximately 30 μm; the Li2S particles prior to ball milling have a particle size of approximately 250 nm to approximately 25 μm; the mixture is ball-milled at approximately 300 to approximately 550 RPM for approximately 1 hour to approximately 5 hours; and the ball milling converts approximately 30% to approximately 70% by weight of the LPSCl particles into LPS particles.

[0233] Ball milling conditions – another example

[0234] In some embodiments, the mixture prior to ball milling comprises: Li2S particles in an amount of about 25% to about 35% by weight based on the total weight of the mixture, and carbon particles in an amount of about 18% to about 20% by weight based on the total weight of the mixture; wherein the carbon particles comprise acetylene black carbon; the ball milling of the mixture is performed at about 400 to 500 RPM for about 1 to 5 hours; and the ball milling converts about 40% to 60% by weight of LPS-X particles into LPS particles.

[0235] Ball milling conditions - additional examples

[0236] For example, when LPS-X contains LPSCl, the mixture prior to ball milling comprises: approximately 25% to approximately 35% by weight of Li2S particles based on the total weight of the mixture, and approximately 18% to approximately 20% by weight of carbon particles based on the total weight of the mixture; wherein the carbon particles comprise acetylene black carbon; the mixture is ball-milled at approximately 400 to 500 RPM for approximately 1 to 5 hours; and the ball milling converts approximately 40% to 60% by weight of LPSCl particles into LPS particles.

[0237] Electrode composite materials

[0238] Another aspect of this disclosure provides an electrode reactivation material comprising: Li2S particles containing a Li2S compound; carbon particles; and solid electrolyte (SE) particles, the solid electrolyte (SSE) particles comprising a first particle containing only a lithium phosphine sulfide (LPS-X) compound, a second particle containing only a lithium phosphine sulfide (LPS) compound, and a third particle containing both LPS and LPS-X compounds, wherein X is selected from the group consisting of F, Cl, Br, I, and combinations thereof, and wherein the XRD of the electrode composite material does not show an XRD peak indicating crystallized LPS-X.

[0239] Furthermore, the XRD of the electrode composite material does not show an XRD peak (211) located at 2θ of approximately 13.7°, which indicates the crystallinity of the LPS compound.

[0240] LPS-X can be LPSF. LPS-X can be LPSCl. LPS-X can be LPSBr. LPS-X can be LPSI. LPS-X can contain any two or more of LPSF, LPSCl, LPSBr, and LPSI. LPS-X can contain LPSF and LPSCl. LPS-X can contain LPSF and LPSBr. LPS-X can contain LPSF and LPSI. LPS-X can contain LPSCl and LPSBr. LPS-X can contain LPSCl and LPSI. LPS-X can contain LPSBr and LPSI. LPS-X can contain LPSF, LPSCl, and LPSBr. LPS-X can contain LPSF, LPSCl, and LPSI. LPS-X can contain LPSF, LPSCl, LPSBr, and LPSI. LPS-X can contain LPSF, LPSCl, LPSBr, and LPSI.

[0241] For example, when LPS-X contains LPSCl, the electrode composite material comprises: Li2S particles containing a Li2S compound; carbon particles; and solid electrolyte (SE) particles, the solid electrolyte (SSE) particles comprising a first particle containing only a lithium phosphorus sulfide (LPSCl) compound, a second particle containing only a lithium phosphorus sulfide (LPS) compound, and a third particle containing both LPS and LPSCl compounds, wherein the XRD of the electrode composite material does not show an XRD peak (111) at approximately 2θ 7.5°, an XRD peak (200) at approximately 2θ 8°, an XRD peak (220) at approximately 2θ 12°, an XRD peak (311) at approximately 2θ 13.5°, and an XRD peak (222) at approximately 2θ 14.5° indicating crystallized LPSCl.

[0242] When LPS-X contains LPSF, the electrode composite material comprises: Li2S particles containing a Li2S compound; carbon particles; and solid electrolyte (SE) particles, wherein the solid electrolyte (SSE) particles comprise a first particle containing only a lithium phosphine sulfide fluoride (Li9PS6F, ​​or "LPSF") compound, a second particle containing only a lithium phosphine sulfide (LPS) compound, and a third particle containing both LPS and LPSF compounds, wherein the XRD of the electrode composite material does not show XRD peaks indicating crystalline LPSF. The ball milling reduces the electrolyte to its decomposition products, as shown by LPSCl. In this case, LPSF is converted to Li2S, LPS, and LiF.

[0243] When LPS-X contains LPSBr, the electrode composite material comprises: Li2S particles containing a Li2S compound; carbon particles; and solid electrolyte (SE) particles, the solid electrolyte (SSE) particles containing only lithium phosphorus sulfide bromide (Li2S) compounds. 10 P3S 12 The electrode composite comprises a first particle containing a Br (or "LPSBr") compound, a second particle containing only a lithium phosphide (LPS) compound, and a third particle containing both LPS and LPSBr compounds, wherein the XRD pattern of the composite does not show an XRD peak indicating crystalline LPSBr. The ball milling reduces the electrolyte to its decomposition products, as shown by LPSCl. In this case, LPSBr is converted to Li₂S, LPS, and LiBr.

[0244] When LPS-X contains LPSI, the electrode composite material comprises: Li2S particles containing a Li2S compound; carbon particles; and solid electrolyte (SE) particles, wherein the solid electrolyte (SSE) particles comprise a first particle containing only a lithium phosphine sulfide iodide (Li9PS7I, or "LPSI") compound, a second particle containing only a lithium phosphine sulfide (LPS) compound, and a third particle containing both LPS and LPSI compounds, wherein the XRD of the electrode composite material does not show XRD peaks indicating crystalline LPSI. The ball milling reduces the electrolyte to its decomposition products, as shown by LPSCl. In this case, LPSI is converted to Li2S, LPS, and LiI.

[0245] LPS-X particle size

[0246] The volume-based average particle size of particles containing only LPS-X can be in the range of about 0.1 μm to about 50 μm, for example, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 or 50 μm or about. In embodiments, the average particle size of these particles can be within a range formed by selecting any two values ​​listed above or selecting any two values ​​in the range of about 0.1 μm to about 50 μm.

[0247] LPS particle size

[0248] The volume-based average particle size of LPS-containing particles can range from about 0.1 μm to about 50 μm, for example, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 or 50 μm or about. In embodiments, the average particle size of these particles can be within a range formed by selecting any two values ​​listed above or selecting any two values ​​within the range of about 0.1 μm to about 50 μm.

[0249] LPS / LPS-X particle size

[0250] The volume-based average particle size of particles containing both LPS and LPS-X can be in the range of about 0.1 μm to about 50 μm, for example, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 or 50 μm or about. In embodiments, the average particle size can be within a range formed by selecting any two values ​​listed above or selecting any two values ​​in the range of about 0.1 μm to about 50 μm.

[0251] Carbon particle type

[0252] The carbon particles may comprise one or more types, such as Super P carbon black, Ketjen black carbon, acetylene black carbon, natural graphite, artificial graphite, expanded graphite, single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), graphene, graphene oxide (GO), reduced graphene oxide (rGO), carbon nanofibers (CNFs), carbon nano-onions, mesoporous carbon, carbon quantum dots (CQDs), carbon aerogels, or bio-derived carbon particles. For example, the carbon particles may comprise one selected from the group consisting of acetylene black (AB) carbon, vapor-grown carbon fibers (VGCF), carbon nanotubes (CNTs), Ketjen black (KB) carbon, and combinations thereof. In some embodiments, the carbon particles may comprise AB carbon.

[0253] carbon particle surface area

[0254] The BET specific surface area of ​​carbon particles can be approximately 20 m². 2 g -1 Approximately 1000 m 2 g -1Within the range, for example: 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, 500, 510 520, 530, 540, 550, 560, 570, 580, 590, 600, 610, 620, 630, 640, 650, 660, 670, 680, 690, 700, 710, 720, 730, 740, 750, 760, 770, 780, 790, 800, 810, 820, 830, 840, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950, 960, 970, 980, 990 or 1000 m 2 g -1 Or approximately. In an embodiment, the BET specific surface area of ​​the carbon particles can be determined by selecting any two values ​​listed above or selecting approximately 20 m². 2 g -1 Approximately 1000 m 2 g -1 The range formed by any two values ​​within the range. For example, in some embodiments, the BET specific surface area of ​​carbon particles can be approximately 70 m². 2 g -1 .

[0255] The LPS particles may contain Li3PS4.

[0256] Li2S particle weight percentage

[0257] Based on the total weight of the electrode composite material, the electrode composite material may contain approximately 20% to approximately 40% by weight of Li₂S particles. For example, based on the total weight of the electrode composite material, the weight percentage of Li₂S particles may be 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, or 40% by weight or approximately thereafter. In embodiments, the weight percentage of Li₂S particles based on the total weight of the electrode composite material may be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​within the range of approximately 20% to approximately 40% by weight.

[0258] carbon particle weight percentage

[0259] Based on the total weight of the electrode composite material, the electrode composite material may contain approximately 15% to approximately 20% carbon particles. For example, based on the total weight of the electrode composite material, the weight percentage of carbon particles may be 15, 16, 17, 18, 19, or 20% by weight or approximately thereafter. In embodiments, the weight percentage of carbon particles based on the total weight of the electrode composite material may be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​within the range of approximately 15% to approximately 20% by weight.

[0260] Li2S particle size

[0261] The particle size of Li₂S particles can be from about 100 nm to about 1 μm. In embodiments, the average particle size of the Li₂S particles can be any value or around 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1 μm. In embodiments, this Li₂S particle size can be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​in the range of about 100 nm to about 1 μm.

[0262] Manufacturing of electrodes and batteries, and electrodes and batteries derived therefrom

[0263] Electrode manufacturing

[0264] One aspect of this disclosure provides a method for manufacturing an electrode for an all-solid-state battery, which involves pressing the electrode composite material provided in this application under a pressure of about 300 MPa to about 500 MPa.

[0265] Electrode composite materials

[0266] According to one aspect of this disclosure, the composite material may comprise: Li2S particles containing a Li2S compound; carbon particles; and solid electrolyte (SE) particles, said solid electrolyte (SSE) particles comprising a first particle containing only a lithium phosphine sulfide (LPS-X) compound, a second particle containing only a lithium phosphine sulfide (LPS) compound, and a third particle containing both LPS and LPS-X compounds, wherein X is selected from the group consisting of F, Cl, Br, I, and combinations thereof, wherein the XRD of the electrode composite material does not show an XRD peak indicating crystallization of LPS-X. Furthermore, the XRD of the electrode composite material does not show an XRD peak (211) located at approximately 13.7° 2θ, which indicates the crystallinity of the LPS compound.

[0267] Electrode composite material made of LPSCl

[0268] For example, when LPS-X contains LPSCl, the electrode composite material comprises: Li2S particles containing a Li2S compound; carbon particles; and solid electrolyte (SE) particles, the solid electrolyte (SSE) particles comprising a first particle containing only a lithium phosphorus sulfide (LPSCl) compound, a second particle containing only a lithium phosphorus sulfide (LPS) compound, and a third particle containing both LPS and LPSCl compounds, wherein the XRD of the electrode composite material does not show an XRD peak (111) at approximately 2θ 7.5°, an XRD peak (200) at approximately 2θ 8°, an XRD peak (220) at approximately 2θ 12°, an XRD peak (311) at approximately 2θ 13.5°, and an XRD peak (222) at approximately 2θ 14.5° indicating crystallinity of LPSCl. Furthermore, the XRD of the electrode composite material does not show an XRD peak (211) at approximately 2θ 13.7°, which indicates the crystallinity of the LPS compound.

[0269] Electrode composite material made of LPSF

[0270] When LPS-X contains LPSF, the electrode composite material comprises: Li2S particles containing a Li2S compound; carbon particles; and solid electrolyte (SE) particles, the solid electrolyte (SSE) particles comprising a first particle containing only a lithium phosphide sulfide fluoride (Li9PS6F, ​​or "LPSF") compound, a second particle containing only a lithium phosphide sulfide (LPS) compound, and a third particle containing both LPS and LPSF compounds, wherein the XRD of the electrode composite material does not show an XRD peak indicating crystalline LPSF. Furthermore, the XRD of the electrode composite material does not show an XRD peak (211) located at approximately 13.7° 2θ, which indicates the crystallinity of the LPS compound.

[0271] Electrode composite material made of LPSBr

[0272] When LPS-X contains LPSBr, the electrode composite material comprises: Li2S particles containing a Li2S compound; carbon particles; and solid electrolyte (SE) particles, the solid electrolyte (SSE) particles containing only lithium phosphorus sulfide bromide (Li2S) compounds. 10 P3S 12 The electrode composite material comprises a first particle containing a Br (or "LPSBr") compound, a second particle containing only a lithium phosphide (LPS) compound, and a third particle containing both LPS and LPSBr compounds, wherein the XRD pattern of the electrode composite material does not show an XRD peak indicating crystalline LPSBr. Furthermore, the XRD pattern of the electrode composite material does not show an XRD peak (211) located at approximately 13.7° 2θ, which indicates the crystallinity of the LPS compound.

[0273] Electrode composite material made of LPSI

[0274] When LPS-X contains LPSI, the electrode composite material comprises: Li2S particles containing a Li2S compound; carbon particles; and solid electrolyte (SE) particles, the solid electrolyte (SSE) particles comprising a first particle containing only a lithium phosphide sulfide iodide (Li9PS7I, or "LPSI") compound, a second particle containing only a lithium phosphide sulfide (LPS) compound, and a third particle containing both LPS and LPSI compounds, wherein the XRD of the electrode composite material does not show an XRD peak indicating crystalline LPSI. Furthermore, the XRD of the electrode composite material does not show an XRD peak (211) located at approximately 13.7° 2θ, which indicates the crystallinity of the LPS compound.

[0275] Other properties of electrode composite materials

[0276] Other properties of the electrode composite material are described in other parts of this disclosure.

[0277] Suppressing pressure

[0278] The electrode composite material provided in this application is pressed at a pressure of about 300 MPa to about 500 MPa, for example, at 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, or 500 MPa or about. The pressure at which the electrode composite material is pressed to manufacture the electrode can be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​within the range of about 300 MPa to about 500 MPa.

[0279] electrode

[0280] Another aspect of this disclosure provides an electrode manufactured using the method described in this application. The electrode can be a positive electrode.

[0281] Manufacturing of all-solid-state lithium batteries

[0282] One aspect of this disclosure provides a method for manufacturing an all-solid-state lithium battery, wherein a positive electrode is prepared according to the method provided in this application, a solid electrolyte layer is disposed, and then a negative electrode is disposed such that the solid electrolyte layer is sandwiched between the positive electrode and the negative electrode.

[0283] All-solid-state batteries

[0284] Another aspect of this disclosure provides an all-solid-state battery manufactured using the method for manufacturing the all-solid-state battery provided in this application. The all-solid-state battery may include: a positive electrode provided in this application; a negative electrode; and a solid electrolyte layer disposed between the positive electrode and the negative electrode, and configured to enable lithium ion transport between the positive electrode and the negative electrode.

[0285] Overview of solid electrolyte layers

[0286] The solid electrolyte layer provided in this application is suitable for and enables lithium-ion diffusion between the positive and negative electrodes. This solid electrolyte layer is electrically connected to both the positive and negative electrodes and provides a conductive path for the movement of charge carriers between them. In some embodiments, the solid electrolyte layer may be formed above and in direct contact with the positive or negative electrode. In other embodiments, other functional layers may be disposed between the solid electrolyte layer and the positive and / or negative electrode.

[0287] Overview of materials used in solid electrolyte layers

[0288] Generally, there are no particular restrictions on the material of the solid electrolyte layer, as long as it can adhere to adjacent layers, has suitable conductivity, and does not cause significant chemical changes in the solid-state battery within its voltage range. For example, the solid electrolyte layer can contain various inorganic solid electrolytes, polymer solid electrolytes, and / or polymer gel electrolytes, but is not limited to these.

[0289] Overview of sulfide-based / sulfide-containing solid electrolyte layers

[0290] In the solid-state battery provided in this application, the solid electrolyte layer may contain sulfide-based / sulfide-containing materials. As used in this application, "sulfide-based / sulfide-containing electrolyte" refers to an electrolyte containing conductive ions (…). For example Li + This invention relates to electrolytes containing sulfur (S) that electrically insulate the positive and negative electrodes of an electrochemical cell. The sulfide-based / sulfide-containing solid electrolyte contains sulfur (S) and exhibits ionic conductivity characteristic of metals belonging to Group 1 or Group 2 of the periodic table. It may include Li-PS-type glasses or Li-PS-type glass ceramics. For example, the sulfide-based / sulfide-containing solid electrolyte materials used in this application may include lithium sulfide, silicon sulfide, germanium sulfide, and boron sulfide. Non-limiting examples of inorganic solid electrolytes may include: x Li2S·yP2S5(x+y=1), Li 3.833 Sn 0.833 As 0.166 S4, Li4SnS4, Li 3.25 Ge 0.25 P 0.75S4, Li2S-P2S0, B2S3-Li2S, 3+y PO 4-x N x ), thiolated LISICON (Li 3.25 Ge 0.25 P 0.75 S4), Li2O-Al2O3-TiO2-P2O5 (LATP), Li2S-P2S5, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, L i2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SnS, Li2S-P2S5-Al2S3, Li2S-GeS2, Li2S-GeS2-ZnS, etc. or their combinations.

[0291] Solid electrolyte layer containing specific sulfides

[0292] In some embodiments of the solid-state battery provided in this application, the sulfide-containing solid electrolyte layer may comprise an inorganic solid electrolyte material. In some embodiments, the sulfide-containing solid electrolyte material includes an inorganic solid electrolyte material. In some embodiments, the sulfide-containing solid electrolyte material may include Li3P7S. 11 Li 10 GeP2S 12 Na3PS4, Li 6-y PS 5-y Cl 1+y (y < 1) and / or at least one of Li6PS5X (X is Cl, Br or I).

[0293] Solid electrolyte layer particle size

[0294] In the solid-state battery provided in this application, the solid electrolyte layer may comprise a solid electrolyte material provided in particulate form. In some embodiments, the volume-based average particle size of the solid electrolyte material, as measured by laser diffraction-type particle size distribution measurement, may be, for example, about 0.1 μm to about 50 μm, about 0.1 μm to about 40 μm, about 0.1 μm to about 30 μm, about 0.1 μm to about 20 μm, about 0.1 μm to about 10 μm, about 0.1 μm to about 5 μm, about 0.1 μm to about 1 μm, about 1 μm to about 50 μm, about 1 μm to about 40 μm, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 1 μm to about 10 μm, about 1 μm to about 5 μm, about 5 μm to about 50μm, about 5μm to about 40μm, about 5μm to about 30μm, about 5μm to about 20μm, about 5μm to about 10μm, about 10μm to about 50μm, about 10μm to about 40μm, about 10μm to about 30μm, about 10μm to about 20μm, about 20μm to about 50μm, about 20μm to about 40μm, about 20μm to about 30μm, about 20μm to about 50μm, about 20μm to about 40μm, about 20μm to about 30μm, about 30μm to about 50μm, about 30μm to about 40μm, about 40μm to about 50μm, etc. In embodiments, the average particle size of the solid electrolyte material can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50 μm or approximately thereafter. In embodiments, the particle size of the solid electrolyte material can be within a range formed by selecting any two values ​​listed above or any two values ​​within the range of approximately 0.1 μm to approximately 50 μm.

[0295] Porosity

[0296] The solid electrolyte layer maintains a suitable porosity to allow lithium ions to move through it. In some embodiments, the porosity of the solid electrolyte layer provided in this application is greater than about 5%, for example, about 5% to about 15%, about 5% to about 14%, about 5% to about 13%, about 5% to about 12%, about 5% to about 11%, about 5% to about 10%, about 5% to about 9%, about 5% to about 8%, about 5% to about 7%, about 5% to about 6%, or any other percentage in the range greater than 5%, such as any other percentage in the range of about 5% to about 15% or 5% to 15%.

[0297] Other aspects

[0298] Other aspects of this disclosure are provided below. Other features, implementations, and embodiments described below apply to all aspects of the invention described above. However, in the event of any conflict between the information discussed above and the information described below, the information in the foregoing sections shall prevail.

[0299] Solid-state lithium-ion batteries

[0300] Solid-state batteries can withstand multiple charge-discharge cycles to an electrical load. A solid-state battery consists of electrodes, namely a positive and a negative electrode, and an electrolyte that allows lithium ions to move between the electrodes. Unlike traditional liquid electrolyte batteries, solid-state batteries do not contain any flowing liquid. Forming a circuit between the electrodes allows current to flow between them. During the charging process of a lithium-ion rechargeable battery, lithium ions are released from the positive electrode and inserted into the active material of the negative electrode. During the discharging process, lithium ions are released from the negative electrode and inserted into the active material of the positive electrode. Energy is transferred as lithium ions reciprocate between the electrodes.

[0301] Solid-state battery composition

[0302] The present invention provides a solid-state battery 100, which includes a positive electrode 102, a negative electrode 104, and a solid electrolyte layer 106 between the positive electrode 102 and the negative electrode 104. Although illustrated by way of example, the solid-state battery 100 does not require all of these components. For example, in some configurations such as an anode-free system, the negative electrode 104 may be omitted.

[0303] Optional additional layers

[0304] The solid-state battery 100 may optionally include additional layers such as a separator layer, a protective layer, a suppression layer, a solid electrolyte interface layer, or a combination thereof.

[0305] protective layer

[0306] For example, a protective layer can be introduced between electrodes 102 and 104 and the solid electrolyte layer 106, and / or between electrode 102 and current collector 110 in an anode-less system. The protective layer can also mitigate dendrite formation (especially on the negative electrode side), thereby improving the overall cycle life and safety of the battery. In some cases, the protective layer can help improve the interfacial stability between the electrode and electrolyte, potentially reducing undesirable side reactions. Furthermore, the protective layer can enhance the mechanical properties of the electrode-electrolyte interface, which can help maintain good contact during cycling.

[0307] Protective layer material

[0308] This protective layer can contain materials such as lithium phosphate, lithium titanate, and lithium lanthanum zirconium oxide (LLZO), which helps prevent unwanted side reactions at the electrode-electrolyte interface. Other options for protective layer materials include, but are not limited to, lithium niobium oxide (LiNbO3), lithium tantalum oxide (LiTaO3), lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), lithium silicate, and lithium boron oxide.

[0309] membrane layer

[0310] In some configurations of the solid-state battery 100, a separator layer may also be included. These separator layers can provide additional mechanical support to the battery structure while still allowing efficient ion transport. The separator layer can also be designed with a gradient structure having properties optimized for contact with both the positive and negative electrode materials. Such a gradient structure can involve, for example, altering the porosity, composition, or surface properties of the separator thickness. In some aspects, the separator surface can be functionalized with ion-conducting groups or coatings to enhance lithium-ion transport at the electrode-separator interface. The separator layer can also be designed as a multilayer by integrating different materials optimized for specific functions, such as a mechanically strong core layer sandwiched between ion-conducting outer layers. The separator layer can also be designed to self-heal, for example, by reforming bonds after mechanical stress, thereby helping to prevent short circuits caused by dendrite growth.

[0311] Diaphragm material

[0312] While traditional liquid electrolyte batteries often employ porous polymer membranes, solid-state batteries can utilize thin ceramic or glass-ceramic layers as membranes. Materials such as LLZO, LATP (lithium aluminum titanium phosphate), or LAGP (lithium aluminum germanium phosphate) can be used for this purpose. Other membrane layer materials suitable for solid-state batteries include lithium oxynitride phosphate (LiPON), lithium lanthanum titanate (LLTO), and lithium garnet-type materials (such as Li6BaLa2Ta2O). 12 ), sulfide materials (such as Li) 10 GeP2S 12 ) as well as polymer-ceramic composites that combine materials such as polyethylene oxide (PEO) with ceramic fillers.

[0313] Solid-state battery cells

[0314] Figure 1 illustrates a cell 101 of a solid-state battery 100 according to one embodiment. The cell 101 includes a positive electrode 102, a negative electrode 104, and a solid electrolyte layer 106 between the positive electrode 102 and the negative electrode 104. The cell 101 may optionally include additional layers such as a separator layer, a protective layer, a suppression layer, a solid electrolyte interface layer, or a combination thereof.

[0315] Cell composition

[0316] As shown in Figure 1, the solid-state battery 100 may include a single cell 101. In other examples, the solid-state battery 100 may include multiple cells, such as at least two cells, at least three cells, or at least four cells. Connecting cells in series can increase the voltage of the solid-state battery 100, and connecting cells in parallel can increase the ampere-hour capacity of the solid-state battery 100.

[0317] Cell size

[0318] The battery cell 101 may have a width w1, a length l1, and a thickness t1.

[0319] Cell thickness

[0320] The thickness t1 of cell 101 can be any value or around the range of approximately 100 μm to approximately 5000 μm, for example, approximately 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, 500, 510, 520, 530, 540, 550, 560, 570, 580, 590, 600, 6 10, 620, 630, 640, 650, 660, 670, 680, 690, 700, 710, 720, 730, 740, 750, 760, 770, 780, 790, 800, 810, 820, 830, 840, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950, 960, 970, 980, 990, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 3000, 4000, or 5000 μm. In some embodiments, the thickness t1 of the cell 101 can be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​in the range of about 100 μm to about 5000 μm, for example, between about 100 μm and about 5000 μm or between about 100 μm and about 1000 μm.

[0321] Aspect Ratio of Width

[0322] The width w1 of the battery cell 101 may be substantially greater than the thickness t1 of the battery cell 101. In some embodiments, the aspect ratio of the width w1 to the thickness t1 may be at least 10, at least 20, at least 30, at least 40, at least 50, at least 60, at least 70, at least 80, at least 90, at least 100, at least 110, at least 120, at least 130, at least 140, at least 150, at least 160, at least 170, at least 180, at least 190, at least 200, at least 210, at least 220, at least 230, at least 240, at least 250, at least 260, or even higher. At least 270, at least 280, at least 290, at least 300, at least 350, at least 400, at least 450, at least 500, at least 550, at least 600, at least 650, at least 700, at least 750, at least 800, at least 850, at least 900, at least 950, at least 1000, at least 2000, at least 3000, at least 4000, at least 5000, at least 6000, at least 7000, at least 8000, at least 9000, or at least 10000.

[0323] Aspect Ratio of Length

[0324] The length l1 of the battery cell 101 may be substantially greater than the thickness t1 of the battery cell 101. In some embodiments, the aspect ratio of the length l1 to the thickness t1 may be at least 10, at least 20, at least 30, at least 40, at least 50, at least 60, at least 70, at least 80, at least 90, at least 100, at least 110, at least 120, at least 130, at least 140, at least 150, at least 160, at least 170, at least 180, at least 190, at least 200, at least 210, at least 220, at least 230, at least 240, at least 250, at least 260, or even higher. At least 270, at least 280, at least 290, at least 300, at least 350, at least 400, at least 450, at least 500, at least 550, at least 600, at least 650, at least 700, at least 750, at least 800, at least 850, at least 900, at least 950, at least 1000, at least 2000, at least 3000, at least 4000, at least 5000, at least 6000, at least 7000, at least 8000, at least 9000, or at least 10000.

[0325] positive electrode

[0326] The positive electrode 102 is associated with one polarity (e.g., positive polarity) of the solid-state battery 100. During the discharge process of the solid-state battery 100, the positive electrode 102 is configured as the positive electrode. The positive electrode 102 is suitable for lithium-ion diffusion between the current collector 108 and the solid electrolyte layer 106. The positive electrode 102 is electrically connected to the current collector 108.

[0327] Positive position

[0328] In one embodiment, the positive electrode 102 is formed above the current collector 108 and is in direct contact with the current collector 108. In other embodiments, other functional layers may be inserted between the positive electrode 102 and the current collector 108.

[0329] Positive electrode materials

[0330] The positive electrode 102 can be capable of reversibly inserting and deintercalating lithium ions. For example, the positive electrode 102 may contain only a positive electrode active material. In other examples, the positive electrode 102 may optionally contain one or more of conductive carbon, solid electrolyte material, and binder. Optionally, the positive electrode 102 may also contain additives, such as oxidation stabilizers, reduction stabilizers, flame retardants, heat stabilizers, antifogging agents, thickeners, plasticizers, ion conductivity enhancers, binders (described in detail below), dispersants, wetting agents, adhesion promoters, crosslinking agents, colorants, etc., or combinations thereof.

[0331] Examples of additives

[0332] Examples of such additives may include: butylated hydroxyanisole (BHA) or butylated hydroxytoluene (BHT) as oxidative stabilizers; ascorbic acid or sodium sulfite as reducing stabilizers; aluminum hydroxide or magnesium hydroxide as flame retardants; phenolic compounds or phosphites as heat stabilizers; polyethylene glycol or silica nanoparticles as antifogging agents; carboxymethyl cellulose (CMC) or xanthan gum as thickeners; dibutyl phthalate or triethyl citrate as plasticizers; ceramic fillers or ionic liquids as ion conductivity enhancers; polyvinylpyrrolidone or sodium dodecyl sulfate as dispersants; polysorbate or poloxamer as wetting agents; silanes or titanates as adhesion promoters; peroxides or aziridines as crosslinking agents; and carbon black or metal oxides as colorants.

[0333] Positive electrode active material

[0334] Positive electrode active materials may include: lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), and Li[Ni a Co b Mn c M 1 d O2 (where M) 1 For any element selected from the group consisting of Al, Ga, In, or combinations thereof, 0.3≤a<1.0, 0≤b≤0.5, 0≤c≤0.5, 0≤d≤0.1, a+b+c+d=1), Li (Li e M 2 f-e-f M 3 f' )O 2-g Ag (where 0≤e≤0.2, 0.6≤f≤1, 0≤f′≤0.2, 0=g≤0.2, M) 2 M contains Mn and at least one element selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn, and Ti. 3 Compounds containing at least one element selected from the group consisting of Al, Mg, and B, where A is at least one element selected from the group consisting of P, F, S, and N, or those compounds substituted by one or more transition metals; such as those with the chemical formula Li. 1+h Mn 2-h Lithium manganese oxides represented by O4 (where 0 ≤ h ≤ 0.33), LiMnO3, LiMn2O3, or LiMnO2; lithium copper oxides (Li2CuO2); vanadium oxides, such as LiV3O8, V2O5, or Cu2V2O7; and those with the chemical formula LiNi. 1-i M 4 i O2 (where M) 4 =Co, Mn, Al, Cu, Fe, Mg, B or Ga, 0.01≤y≤0.3) represents Ni-type lithium nickel oxide; chemical formula LiMn 2-j M 5 j O2 (where M) 5 =Co, Ni, Fe, Cr, Zn or Ta, 0.01≤y≤0.1) or Li2Mn3M 6 O8 (where M) 6 Lithium manganese composite oxides represented by Fe, Co, Ni, Cu or Zn; LiMn2O4 in which Li is partially substituted by alkaline earth metal ions; disulfide compounds; LiFe3O4, Fe2(MoO4)3, etc.; or combinations thereof.

[0335] Phosphate materials

[0336] Besides the aforementioned positive electrode active materials, the positive electrode can also contain other types of materials. For example, lithium iron phosphate (LiFePO4) can be used as a positive electrode active material due to its excellent thermal stability and long cycle life. Another example is lithium manganese iron phosphate (LiMn). x Fe 1-x Other phosphate materials such as lithium vanadium phosphate (LiVOPO4), lithium titanium phosphate (LiTi2(PO4)3), lithium nickel phosphate (LiNiPO4), fluorophosphates such as LiVPO4F or LiFeSO4F, or lithium cobalt phosphate (LiCoPO4) are also suitable.

[0337] Layered oxide materials

[0338] Positive electrode active materials can also include layered oxide materials with various compositions, such as Li(Ni) 1-x- y Co x Mn y O2 (NCM) or Li (Ni) 1-x-y Co x Al y O2 (NCA), in which the ratio of Ni, Co, Mn, and Al can be adjusted to optimize performance characteristics. For example, NCM811 (LiNi) can be used. 0.8 Co 0.1 Mn 0.1 Higher energy density can be achieved using NCM materials with high nickel content, such as O2. 0.5 Mn 1.5 Spinel structures such as O4 can provide high-voltage operation. Alternatively, materials with ideal structures, such as LiFeSO4F or LiVPO4F, can be used due to their potential for high energy density and good thermal stability.

[0339] Composite or hybrid cathode materials

[0340] Composite or hybrid cathode materials combining two or more active materials can also be used. For example, a mixture of layered oxides and spinel materials can be used to balance energy density and power performance. As another example, lithium iron phosphate can be mixed with one or more of the aforementioned cathode active materials. In some embodiments, the cathode active material may comprise a surface-modified form of the aforementioned compounds, wherein the surface modification is intended to improve stability, conductivity, or other performance indicators.

[0341] Emerging materials category

[0342] Cathode active materials can also include emerging material categories such as disordered rock salt structures (e.g., Li3NbO4-type materials), lithium-rich anti-perovskites (e.g., Li3OCl), cationic disordered oxides (e.g., Li-Mn-VO systems), or high-entropy oxides, which can provide an ideal combination of high capacity and structural stability. In some cases, dopants or substitution elements can be introduced into cathode active materials to further modulate their electrochemical properties.

[0343] Particle properties of positive electrode active materials

[0344] The positive electrode active material can be in particle shape. The particle size of the positive electrode active material can range from about 1 nm to about 1000 μm, for example, about 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, 260 nm, 270 nm, 280 nm, 290 nm, 300 nm, 310 nm, 320 nm, 330 nm, 340 nm, 350 nm, 360 nm, 370 nm, 380 nm, 390 nm, 400 nm, 410 nm, 420 nm, 430 nm, 440 nm, 450 nm, 460 nm. nm, 470 nm, 480 nm, 490 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm, 900 nm, 950 nm, 1000 nm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, 300 μm, 310 μm, 320 μm, 330 μm, 340 μm, 350 μm, 360 μm, 370 μm, 380 μm, 390 μm, 400 μm, 410 µm, 420 µm, 430 µm, 440 µm, 450 µm, 460 µm, 470 µm, 480 µm, 490 µm, 500 µm, 550 µm, 600 µm, 650 µm, 700 µm, 750 µm, 800 µm, 850 µm, 900 µm, 950 µm or 1,000 Any value in μm.In this embodiment, the particle size of the positive electrode active material can be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​in the range of about 1 nm to about 1,000 μm, for example, about 10 nm to about 1,000 μm. The gaps between the positive electrode active material particles in the positive electrode 102 can be filled with a solid electrolyte material.

[0345] The amount of positive electrode active material in the positive electrode

[0346] The amount of positive electrode active material in the solid-state battery 100 affects the charge / discharge capacity of the solid-state battery 100. To manufacture a high-capacity positive electrode 102, a high level of positive electrode active material can be included in the positive electrode 102. For example, based on the total weight of the positive electrode 102, the positive electrode 102 may contain approximately or more of the positive electrode active material at or above 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 98, or 99% by weight. In embodiments, the positive electrode active material in the positive electrode 102 can be within a range formed by selecting any two values ​​listed above or any two values ​​within the range of 0 to 100% by weight, for example, approximately 40% to approximately 98% by weight.

[0347] Conductive material in the positive electrode

[0348] There are no specific restrictions on the conductive material in the positive electrode 102, as long as it is conductive and does not cause chemical changes in the corresponding solid-state battery 100. For example, the conductive material may include: graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermally cracked carbon black; conductive fibers, such as carbon fibers or metal fibers; carbon nanotubes (CNTs), including single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs); fluorinated carbon; metal powders such as aluminum powder or nickel powder; conductive whiskers, such as zinc oxide or potassium titanate; conductive metal oxides, such as titanium oxide; conductive polymers, such as polyphenylene derivatives; graphene, metal nanowires (e.g., silver nanowires), indium tin oxide (ITO), antimony-doped tin oxide (ATO), fluorine-doped tin oxide (FTO), aluminum-doped zinc oxide (AZO), gallium-doped zinc oxide (GZO), conductive ceramics (such as titanium nitride or titanium carbide), etc., or combinations thereof.

[0349] The amount of conductive material in the positive electrode

[0350] Based on the total weight of the positive electrode 102, the positive electrode 102 contains 1, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30% by weight or about of conductive material. In an embodiment, the content of conductive material in the positive electrode 102 can be within a range formed by selecting any two values ​​listed in the preceding sentence, for example, from about 1% by weight to about 30% by weight.

[0351] Adhesive materials

[0352] Adhesives may contain various types of adhesive polymers, such as: vinylidene fluoride-hexafluoropropylene copolymer (PVdF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylate, ethylene propylene diene monomer (EPDM), sulfonated ethylene propylene diene monomer (EPDM), styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, polyimide, polyamide-imide, polyurethane, polyethylene oxide (PEO), poly(ethylene-vinyl acetate) (PEVA), polyvinyl acetate (PVA), chitosan, guar gum (GG), xanthan gum, carrageenan, pectin, water-soluble polymers, lignin, polymers whose hydrogen atoms are replaced by Li, Na, or Ca, various copolymers thereof, or combinations thereof.

[0353] Other adhesive materials

[0354] In addition to the aforementioned adhesive materials, other types of adhesive materials can be used in the positive electrode to improve its performance and stability. For example, water-soluble adhesives such as sodium alginate, gelatin, or polyacrylamide can be used to improve the environmental friendliness of the electrode manufacturing process. These adhesives can also provide advantages in terms of electrode flexibility and adhesion strength. In some cases, conductive adhesives such as poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) or polyaniline (PANI) can be used to simultaneously improve the mechanical integrity and conductivity of the electrode.

[0355] Novel adhesive system

[0356] Novel adhesive systems, such as self-healing polymers or supramolecular assemblies, can be introduced to enhance the long-term stability and cycle life of batteries. Furthermore, composite adhesives that combine or incorporate multiple polymers with inorganic nanoparticles can be used to customize the mechanical, thermal, and electrochemical properties of the electrodes. In some embodiments, bio-derived or biodegradable adhesives, such as cellulose derivatives or chitosan, can be used to reduce the environmental impact of battery production and disposal.

[0357] Amount of binder in the positive electrode

[0358] Based on the total weight of the positive electrode 102, the positive electrode 102 may contain 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30% by weight or about the amount of binder. In an embodiment, the binder content in the positive electrode 102 can be within a range formed by selecting any two values ​​listed in the preceding sentence, for example, from about 1% by weight to about 30% by weight.

[0359] solid electrolyte materials

[0360] The solid electrolyte material in the positive electrode 102 may be configured to be the same as the material of the solid electrolyte layer 106 described below. The solid electrolyte material in the positive electrode 102 may be the same as or different from the material of the solid electrolyte layer 106.

[0361] The amount of solid electrolyte material in the positive electrode

[0362] Based on the total weight of the positive electrode 102, the positive electrode 102 may contain approximately 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30% by weight of solid electrolyte material. In an embodiment, the amount of solid electrolyte material in the positive electrode 102 may be within a range formed by selecting any two values ​​listed in the preceding sentence, for example, from approximately 1% by weight to approximately 30% by weight.

[0363] Positive electrode thickness

[0364] The thickness t2 of the positive electrode 102 can be any value greater than or around 0 to 1000 μm, such as 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490 μm. 500, 510, 520, 530, 540, 550, 560, 570, 580, 590, 600, 610, 620, 630, 640, 650, 660, 670, 680, 690, 700, 710, 720, 730, 740, 75 0, 760, 770, 780, 790, 800, 810, 820, 830, 840, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950, 960, 970, 980, 990, 1000 μm. In an implementation, the thickness t2 of the positive electrode 102 can be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​in the range of greater than 0 to about 1000 μm, for example, about 10 μm to about 1000 μm.

[0365] Positive electrode porosity

[0366] Based on the total volume of the positive electrode 102, the porosity of the positive electrode 102 can be any value in the range of 0 to 20 volume %, or around it, for example, 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, or 18 volume %, or any other volume %, in the range of 0 to 20 volume %. In an embodiment, the porosity of the positive electrode 102 can be within a range formed by selecting any two values ​​listed above or selecting any two values ​​in the range of 0 to 20 volume %, for example, from 0 volume % to about 18 volume %.

[0367] Lithium-ion diffusion properties of the positive electrode

[0368] The positive electrode 102 can be contained in a range greater than 0 to 1 × 10 -7 cm 2 Lithium-ion diffusivity of any value in the range of / s or around it, for example, 1×10 -14 cm 2 / s, 1×10 -13 cm 2 / s, 1×10 -12 cm2 / s, 1×10 -11 cm 2 / s, 1×10 -10 cm 2 / s, 1×10 -9 cm 2 / s, 1×10 -8 cm 2 / s or 1×10 -7 cm 2 / s. In an implementation, the lithium-ion diffusion of the positive electrode 102 can be achieved by selecting any two values ​​listed above or selecting values ​​greater than 0 to 1 × 10⁻⁶. -7 cm 2 The range formed by any two values ​​within the range of / s, for example, 1×10 -14 cm 2 / s to approximately 1×10 -7 cm 2 / s.

[0369] Positive current collector

[0370] The current collector 108 collects the electrical energy generated at the positive electrode 102 and supports the positive electrode 102.

[0371] Materials used for current collectors at the positive electrode

[0372] The material of the current collector 108 is not particularly limited, as long as it can adhere to the positive electrode 102, has suitable conductivity, and does not cause significant chemical changes in the solid-state battery 100 within the voltage range of the corresponding solid-state battery 100. For example, the current collector 108 can be made of or contain various materials, such as metals, conductive carbon, or conductive ceramics, but is not limited thereto. The metal of the current collector 108 may include, but is not limited to, one or more of the following groups: aluminum, aluminum alloys, copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, iron, iron alloys (e.g., steel, stainless steel), silver, silver alloys, gold, platinum, palladium, chromium, molybdenum, tungsten, tantalum, niobium, zirconium, vanadium, manganese, cobalt, indium, tin, lead, bismuth, or combinations thereof.

[0373] Current collector geometry

[0374] The current collector 108 can also be configured in various other geometries to optimize its performance and integration with the positive electrode 102, and its size can be adjusted for specific shape factors such as pouch, cylindrical and / or prismatic shape factors.

[0375] The shape of the current collector at the positive electrode

[0376] By forming fine surface irregularities on the surface of the current collector 108, the adhesion of the positive electrode 102 to the current collector 108 can be improved. The current collector 108 can have various shapes, such as a film, sheet, foil, mesh, porous body, foam, nonwoven mesh, or a combination thereof.

[0377] Examples of the shape and size of current collectors

[0378] For example, the current collector 108 can be configured as a mesh or grid, which can provide enhanced mechanical support while maintaining the high surface area required for electrode adhesion. In some embodiments, the current collector 108 can be designed with a corrugated or wavy pattern, which potentially increases the contact area with the positive electrode material and improves overall conductivity. The current collector 108 can also be fabricated as a perforated sheet, allowing for better electrolyte permeation and ion transport. In some cases, the current collector 108 can be formed as a three-dimensional structure, such as a fiber interconnect network or a honeycomb configuration, which can enhance the structural integrity of the electrode assembly while promoting efficient current harvesting.

[0379] Thickness of the current collector at the positive electrode

[0380] The thickness t3 of the current collector 108 can be any value greater than or around 0 to 500 μm, such as 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, or 500 μm. In an implementation, the thickness t3 of the current collector 108 can be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​in the range greater than 0 to 500 μm, for example, about 5 μm to about 500 μm.

[0381] Method for manufacturing positive electrode

[0382] Positive electrode 102 can be obtained through various methods.

[0383] Dry powder coating process

[0384] For example, a dry powder coating process can be used, in which the positive electrode active material, conductive additives, and binder are mixed in a dry state and then directly coated onto the current collector 108 using electrostatic deposition or mechanical compression. This method can reduce environmental impact by reducing solvent usage.

[0385] 3D printing

[0386] In some cases, the positive electrode 102 can be fabricated using additive manufacturing techniques such as 3D printing. This method allows for precise control of the electrode structure and porosity, potentially improving electrode performance and energy density. Depending on the specific material and desired electrode properties, various 3D printing methods can be employed, including fused deposition modeling (FDM), selective laser sintering (SLS), or direct ink writing (DIW).

[0387] electrospinning

[0388] Another method for manufacturing the positive electrode 102 involves electrospinning. In this process, a solution containing a positive electrode active material, conductive additives, and a polymer binder is extruded through a nozzle under an electric field to form nanofibers. These fibers can be directly collected on the current collector 108 to form a highly porous electrode structure with an increased surface area.

[0389] Casting

[0390] In some embodiments, the positive electrode 102 can be prepared using a casting process. This technique involves spreading a slurry of electrode material onto a moving carrier film using a doctor blade, followed by drying and calendering. The resulting electrode strip can then be laminated onto the current collector 108.

[0391] Spraying

[0392] Alternatively, the positive electrode 102 can be prepared using a spray coating technique. In this method, compressed air or ultrasonic atomization is used to spray a micro-mist of the electrode slurry onto the current collector 108. This process can achieve the formation of a thin and uniform electrode layer, and is particularly suitable for large-scale production.

[0393] Cryogenic casting

[0394] In some cases, the positive electrode 102 can be prepared using a cryogenic casting method. This process involves freezing a slurry of electrode material and then sublimating the ice to form a porous structure. The resulting porous electrode can then be sintered and attached to the current collector 108.

[0395] Sol-gel method

[0396] For some applications, the positive electrode 102 can be prepared using a sol-gel method. This method involves forming a colloidal suspension (sol), which is then transformed into a gel-like network containing the positive electrode active material and other components. This gel can be coated onto the current collector 108 and then heat-treated to form the final electrode structure.

[0397] Slurry-based processes

[0398] For example, the positive electrode active material can be mixed with a solvent and optionally a binder, conductive material and dispersant and stirred to form a slurry. The slurry can then be coated (e.g., coated) onto the current collector 108, followed by pressing and drying to obtain the positive electrode 102.

[0399] Coating method for positive electrode slurry

[0400] Applying the slurry to the positive electrode 102 may include using techniques selected from the group consisting of: slot coating, gravure coating, spin coating, spray coating, roller coating, curtain coating, extrusion, casting, screen printing, inkjet printing, spray printing, gravure printing, heat transfer printing, letterpress printing, intaglio printing, offset printing, and combinations thereof.

[0401] Double-layer slot coating

[0402] In some embodiments, the positive electrode 102 can be prepared using a double-slit coating (DLD) technique. This method involves simultaneously applying two different electrode materials to the current collector 108 in a single operation. The DLD process enables the creation of a gradient structure within the electrode, potentially optimizing both the electrochemical performance and mechanical properties of the positive electrode. Furthermore, this technique allows for the introduction of functional intermediate layers or protective coatings as part of the electrode fabrication process, potentially improving overall battery performance and lifespan.

[0403] Solvent for positive electrode slurry

[0404] The solvent used for forming the positive electrode 102 may contain water and / or organic solvents, such as N-methylpyrrolidone (NMP), dimethylformamide (DMF), acetone, dimethylacetamide, dimethyl sulfoxide (DMSO), isopropanol, etc., or combinations thereof. Considering factors such as slurry coating thickness, productivity, etc., or combinations thereof, the solvent may be used in an amount sufficient to dissolve and disperse electrode components such as positive electrode active materials, binders, and conductive materials. Other solvents that may be used include ethanol, methanol, propanol, butanol, ethyl acetate, methyl ethyl ketone, tetrahydrofuran, diethyl ether, and toluene.

[0405] Solvent-free method

[0406] In some aspects of this disclosure, the cathode 102 can be prepared using solvent-free methods, such as dry powder processing or melt extrusion, which can reduce the use of liquid solvents and provide environmental and cost benefits.

[0407] Dispersant for positive electrode slurry

[0408] The dispersant forming the positive electrode 102 may include aqueous or organic dispersants, such as N-methyl-2-pyrrolidone. Other possible dispersants may include polyvinylpyrrolidone (PVP), carboxymethyl cellulose (CMC), sodium dodecyl sulfate (SDS), Triton X-100, polyethylene glycol (PEG), polyacrylic acid (PAA), and various surfactants such as polysorbate or poloxamer.

[0409] Drying technology for cathode slurry

[0410] The slurry for cathode 102 can be dried by irradiation with heat, electron beam (E-beam), gamma rays, or ultraviolet light (G / H / I lines), or a combination thereof, causing the solvent to vaporize. For example, the slurry can be vacuum dried at room temperature. Although the solvent is removed by evaporation through the drying step, other components do not evaporate and remain intact to form cathode 102.

[0411] Other drying techniques

[0412] In addition to the drying technology described above, the positive electrode 102 can also be dried using other methods such as infrared (IR) drying, microwave drying, or freeze drying.

[0413] Combination of drying technologies

[0414] In some implementations, a combination of drying techniques may be used, such as using convection heating followed by vacuum drying, to optimize the drying process and ensure complete solvent removal while maintaining the integrity of the electrode structure.

[0415] Negative electrode overview

[0416] The negative electrode 104 is associated with a polarity (e.g., negative) of the solid-state battery 100, which is different from the polarity of the positive electrode 102. During the discharge process of the solid-state battery 100, the negative electrode 104 is configured as the negative electrode. The negative electrode 104 is suitable for lithium-ion diffusion between the current collector 110 and the solid electrolyte layer 106.

[0417] Negative electrode position

[0418] The negative electrode 104 is electrically connected to the current collector 110. In one embodiment, the negative electrode 104 is formed above the current collector 110 and is in direct contact with the current collector 110. In other embodiments, other functional layers may be inserted between the negative electrode 104 and the current collector 110.

[0419] Anode-free electrode system

[0420] In some embodiments, as described above, the solid-state battery 100 may employ an anode-less electrode system. In such a configuration, the negative electrode 104 can be omitted, and lithium metal can be directly deposited onto the current collector 110 during charging. This method can potentially increase the energy density of the battery, eliminate the need for a separate negative electrode material, and also potentially reduce the overall thickness of the battery structure.

[0421] negative electrode materials

[0422] The negative electrode 104 can be capable of reversibly inserting and deintercalating lithium ions. For example, the negative electrode 104 may contain only the negative electrode active material. In other examples, the negative electrode 104 may contain conductive particles, binders, etc., or combinations thereof.

[0423] Additives for negative electrodes

[0424] Optionally, the negative electrode 104 may also contain additives, such as oxidation stabilizers (e.g., butylated hydroxyanisole, butylated hydroxytoluene, propyl gallate, tert-butylhydroquinone), reduction stabilizers (e.g., ascorbic acid, sodium sulfite, isoascorbic acid, sodium metabisulfite), flame retardants (e.g., aluminum hydroxide, magnesium hydroxide, ammonium polyphosphate, melamine cyanurate), heat or light stabilizers (e.g., phenolic compounds, phosphites, hindered amine light stabilizers, UV absorbers, such as benzophenone or benzotriazole), antifogging agents (e.g., polyethylene glycol, silica nanoparticles, glycerin, sorbitol), thickeners (e.g., carboxymethyl cellulose, xanthan gum), etc., or combinations thereof.

[0425] Other additives for the negative electrode

[0426] In addition, conductive additives such as carbon black, graphene, or carbon nanotubes can be incorporated to enhance conductivity, while adhesive modifiers such as styrene-butadiene rubber or polyacrylic acid can improve adhesion and mechanical stability. Functional additives such as fluoroethylene carbonate or vinylene carbonate may also be included to promote the formation of a stable solid electrolyte interface layer on the negative electrode surface.

[0427] Materials for negative electrode active materials

[0428] The negative electrode active material is made of or contains various materials, such as alkali metals, alkaline earth metals, group 3B metals, transition metals, metalloids, their alloys, conductive carbon, or combinations thereof, but is not limited thereto. In embodiments, the negative electrode active material may contain silicon, silicon alloys, lithium, lithium alloys, conductive carbon, or combinations thereof, but is not limited thereto. In embodiments, the lithium alloy is made of or contains a lithium alloy containing silicon, chlorine, or a combination thereof. A lithium metal thin film can be used as the negative electrode active material.

[0429] Other materials for negative electrode active materials

[0430] The negative electrode active material may include: carbon-based materials such as artificial graphite, natural graphite, graphitized carbon fibers or amorphous carbon; metal compounds capable of being alloyed with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys or Al alloys; metal oxides capable of doping and undoping lithium ions, such as SiO x (0<x<2), SnO2, vanadium oxide or lithium vanadium oxide; or composites comprising a metal compound and a carbon-based material, such as Si-C composites or Sn-C composites.

[0431] Carbon-based materials

[0432] The carbon-based material may include low-crystallinity carbon, high-crystallinity carbon, or a combination thereof. Representative examples of low-crystallinity carbon are soft carbon and hard carbon. Representative examples of high-crystallinity carbon are amorphous, plate-shaped, flake-shaped, spherical or fibrous natural graphite or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microbeads, mesophase pitch, and high-temperature calcined carbon such as coke derived from petroleum or coal tar pitch, or a combination thereof.

[0433] Metal-carbon composite material

[0434] Alternatively, according to some aspects of the present disclosure, the negative electrode 104 may comprise a negative electrode active material having a metal-carbon composite material, for example, a silver-carbon mixture or composite material, wherein silver particles are composited between amorphous and / or crystalline carbon particles. Silver is taken as an example here, and other metals can also be used, including for example tin and / or zinc. Silicon can be used instead of silver.

[0435] Additional materials for negative electrode active materials

[0436] In addition to the aforementioned materials, the negative electrode active material may also include titanium-based compounds, such as lithium titanate (Li4Ti5O 12 ) or titanium dioxide (TiO2), which can provide excellent cycle stability and high rate performance. Other potential materials may include transition metal oxides, such as molybdenum oxide (MoO x ), iron oxide (FeO x ) or nickel oxide (NiO x ), which can provide a high theoretical capacity. In some cases, a composite active material combining different active materials, such as a silicon-graphite composite or a tin-carbon composite, can be used to take advantage of multiple materials while alleviating their individual limitations.

[0437] Dendrite formation

[0438] When the negative electrode 104 is made of or contains lithium or a lithium alloy, dendrites may form on the negative electrode 104. Dendrites are metallic lithium structures formed when excess lithium ions accumulate on the surface of the negative electrode 104. The formed dendrites may damage the solid electrolyte layer 106, reduce the battery capacity of the solid-state battery 100, and / or cause undesirable performance of the solid-state battery 100. Dendrite formation is a major challenge for lithium-ion batteries because these structures can grow through the electrolyte, potentially causing short circuits and safety hazards. The growth rate and morphology of dendrites can be affected by factors such as current density, temperature, and the properties of the electrolyte-electrode interface.

[0439] Advantages of solid electrolytes in mitigating dendrite formation

[0440] Solid electrolytes offer several advantages over liquid electrolytes in mitigating dendrite formation. The mechanical strength of solid electrolytes helps suppress dendrite growth by providing a physical barrier to lithium metal penetration. Furthermore, the uniform ion distribution in solid electrolytes promotes more uniform lithium deposition, reducing the likelihood of localized dendrite nucleation. Some solid electrolytes can also form stable interfaces with lithium metal anodes, further suppressing dendrite formation. However, while solid electrolytes can significantly reduce the risk of dendrite growth, they cannot completely eliminate it. Current research focuses on developing advanced solid electrolyte materials with enhanced dendrite suppression capabilities.

[0441] Shape of negative electrode active material

[0442] The negative electrode active material can be in particulate form or in a continuous single form (e.g., thin film or sheet).

[0443] Particle size

[0444] In embodiments where the negative electrode active material is in particulate form, the negative electrode active material can have a particle size of any value in the range of about 10 nm to about 1000 μm, such as about 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, 260 nm, 270 nm, 280 nm, 290 nm, 300 nm, 310 nm, 320 nm, 330 nm, 340 nm, 350 nm, 360 nm, etc. nm, 370 nm, 380 nm, 390 nm, 400 nm, 410 nm, 420 nm, 430 nm, 440 nm, 450 nm, 460 nm, 470 nm, 480 nm, 490 nm, 500 nm, 510 nm, 520 nm, 530 nm, 540 nm, 550 nm, 560 nm, 570 nm, 580 nm, 590 nm, 600 nm, 610 nm, 620 nm, 630 nm, 640 nm, 650 nm, 660 nm, 670 nm, 680 nm, 690 nm, 700 nm, 710 nm, 720 nm, 730 nm, 740 nm, 750 nm, 760 nm, 770 nm, 780 nm, 790 nm, 800 nm, 810 nm, 820 nm, 830 nm, 840 nm, 850 nm, 860 nm, 870 nm, 880 nm, 890 nm, 900 nm, 910 nm, 920 nm, 930 nm, 940nm, 950 nm, 960 nm, 970 nm, 980 nm, 990 nm, 1000 nm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, 300 μm, 310 μm, 320 μm, 330 μm, 340 μm, 350 μm, 360 μm, 370 μm, 380 μm, 390 μm, 400 μm, 410 μm, 420 μm, 430 μm, 440 μm, 450 μm, 460 μm, 470 μm, 480 μm, 490 μm, 500 μm, 510 μm, 520 μm, 530 μm, 540 μm, 550 μm, 560 μm, 570 μm, 580 μm, 590 μm, 600 μm, 610 μm, 620 μm, 630 μm, 640 μm, 650 μm, 660 μm, 670 μm, 680 μm, 690 μm, 700 μm, 710 μm, 720 μm, 730 μm, 740 μm, 750 μm, 760 μm, 770 μm, 780 μm, 790 μm, 800 μm, 810 μm, 820 μm, 830 μm, 840 μm, 850 μm, 860 μm, 870 μm, 880 μm, 890 μm, 900 μm, 910 μm, 920 μm, 930 μm, 940 μm, 950 μm, 960 μm, 970 μm, 980 μm, 990 μm, or 1,000 μm or about thereafter. In an embodiment, the particle size of the negative electrode active material can be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​in the range of about 10 nm to about 1,000 μm, for example, about 10 nm to about 1,000 μm.

[0445] The amount of negative electrode active material in the negative electrode

[0446] The amount of negative electrode active material in the solid-state battery 100 affects the charge / discharge capacity of the solid-state battery 100. To manufacture a high-capacity negative electrode 104, a high level of negative electrode active material can be included in the negative electrode 104. For example, based on the total weight of the negative electrode 104, the negative electrode 104 contains approximately or more of 70, 80, 90, 95, 98, 99, or 100% by weight of negative electrode active material. In embodiments, the content of negative electrode active material in the negative electrode 104 can be within a range formed by selecting any two values ​​listed in the preceding sentence, for example, from approximately 70% by weight to approximately 100% by weight.

[0447] Adhesive material in negative electrode

[0448] Adhesives may include various types of adhesive polymers, such as vinylidene fluoride-hexafluoropropylene copolymer (PVdF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylate, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, polymers in which hydrogen atoms are substituted by Li, Na or Ca, various copolymers thereof, or combinations thereof.

[0449] Examples of binder materials used in negative electrodes

[0450] In addition to the aforementioned adhesives, other suitable adhesives for the negative electrode may include polyimide, polyamide-imide, polyurethane, polyethylene oxide (PEO), poly(ethylene-co-vinyl acetate) (PEVA), polyvinyl acetate (PVA), alginate, chitosan, guar gum, xanthan gum, carrageenan, pectin, gelatin, lignin, and various water-soluble polymers or their derivatives. In some cases, conductive polymers such as polypyrrole, polyaniline, or poly(3,4-ethylenedioxythiophene) (PEDOT) may also be used as adhesives to simultaneously improve adhesion and conductivity within the negative electrode.

[0451] The amount of binder in the negative electrode

[0452] Based on the total weight of the negative electrode 104, the negative electrode 104 may contain 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30% by weight, or any other percentage by weight within the range of 0 to 30% by weight. In an embodiment, the adhesive in the negative electrode 104 may be within a range formed by selecting any two values ​​listed above or selecting any two values ​​within the range of 0 to 30% by weight, for example, from about 0% to about 30% by weight.

[0453] negative electrode thickness

[0454] The thickness of the negative electrode 104 can be 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or 100 μm or approximately thereafter. In an embodiment, the thickness t4 of the negative electrode 104 can be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​in the range of approximately 10 μm to approximately 100 μm, for example, approximately 10 μm to approximately 100 μm or approximately 10 μm to approximately 20 μm.

[0455] Negative electrode porosity

[0456] Based on the total volume of the negative electrode 104, the porosity of the negative electrode 104 can be about 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 or 18 volume%, or any other volume% within the range of 0 to 18 volume%. In an embodiment, the porosity of the negative electrode 104 can be within a range formed by selecting any two values ​​listed above or selecting any two values ​​within the range of 0 to about 18 volume%.

[0457] Lithium-ion diffusion of the negative electrode

[0458] The negative electrode 104 can have 1×10 -14 cm 2 / s, 1×10 -13 cm 2 / s, 1×10 -12 cm 2 / s, 1×10 -11 cm 2 / s, 1×10 -10 cm 2 / s, 1×10 -9 cm 2 / s, 1×10 -8 cm 2 / s or 1×10 -7 cm 2 The lithium-ion diffusion rate is approximately 1 × 10⁻⁶ / s or similar. In this embodiment, the lithium-ion diffusion rate of the negative electrode 104 can be achieved by selecting any two values ​​listed above or selecting approximately 1 × 10⁻⁶ / s. -14 cm 2 / s to approximately 1×10 -7 cm 2 The range formed by any two values ​​within the range of / s.

[0459] negative current collector

[0460] The current collector 110 collects the electrical energy generated by the negative electrode 104 and supports the negative electrode 104.

[0461] Materials used for current collectors at the negative electrode

[0462] The material of the current collector 110 is not particularly limited, as long as it can adhere to the negative electrode 104, has suitable conductivity, and does not cause significant chemical changes in the solid-state battery 100 within the voltage range of the corresponding solid-state battery 100. For example, the current collector 110 may be made of or contain metal or conductive carbon, but is not limited to these materials.

[0463] metal for current collector

[0464] The metal of the current collector 110 may include, but is not limited to, one or more of the group consisting of aluminum, aluminum alloy, copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, iron, iron alloy (e.g., steel, stainless steel), silver, silver alloy, or combinations thereof.

[0465] The shape of the current collector at the negative electrode

[0466] By forming fine surface irregularities on the surface of the current collector 110, the adhesion of the negative electrode 104 to the current collector 110 can be improved. The current collector 110 can have various shapes, such as films, sheets, foils, meshes, porous bodies, foams, nonwoven meshes, or combinations thereof. In addition to the shapes mentioned above, the current collector 110 can also be configured as a honeycomb structure, perforated sheet, manufactured / unmanufactured mesh, sintered porous body, or three-dimensional interconnect network. These various shapes can be customized to optimize the surface area, mechanical strength, and current collection efficiency of the current collector 110.

[0467] Design of the current collector for the negative electrode

[0468] In addition, the current collector 110 can be designed to adapt to different shape factors of solid-state batteries such as pouch cells, cylindrical cells or prismatic cells, each of which can provide advantages in terms of packaging efficiency, thermal management and overall battery performance.

[0469] Thickness of the current collector of the negative electrode

[0470] The thickness t5 of the current collector 110 can be 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 55, 60, 65, 70, 75, 80, or 85 mm. The thickness t5 of the current collector 110 can be approximately 500 μm or 90, 95, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, or 500 μm. In an embodiment, the thickness t5 of the current collector 110 can be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​in the range of approximately 1 μm to approximately 500 μm, for example, approximately 5 μm to approximately 500 μm.

[0471] Method for manufacturing the negative electrode

[0472] The negative electrode 104 can be obtained by various methods, such as atomic deposition, extrusion, rolling, slurry processing, or combinations thereof. In addition to the methods described above, the negative electrode 104 can also be manufactured using a variety of other technologies, including dry electrode processes. These alternative methods offer advantages in terms of environmental impact, cost-effectiveness, and scalability.

[0473] Dry powder coating

[0474] Dry powder coating can be used as an alternative to the slurry method. In this method, the negative electrode active material, conductive additives, and binder are mixed in a dry state and then directly coated onto the current collector 110 using electrostatic deposition or mechanical compression. This method can reduce solvent use, potentially reducing environmental impact and processing time.

[0475] 3D printing

[0476] The negative electrode 104 can be fabricated using additive manufacturing technologies such as 3D printing. Depending on the specific material and desired electrode properties, various 3D printing methods can be employed, including fused deposition modeling (FDM), selective laser sintering (SLS), or direct ink writing (DIW). This method allows for precise control of the electrode structure and porosity.

[0477] electrospinning

[0478] Electrospinning is another potential method for manufacturing the negative electrode 104. In this process, a solution containing the negative electrode active material, conductive additives, and polymer binder is extruded through a nozzle under an electric field to form nanofibers. These fibers can be directly collected on the current collector 110 to form a highly porous electrode structure with increased surface area.

[0479] Casting

[0480] The negative electrode 104 can be prepared by tape casting. This technique involves spreading a slurry of electrode material onto a moving carrier film using a doctor blade, followed by drying and calendering. The resulting electrode strip can then be laminated onto the current collector 110.

[0481] Spraying

[0482] The negative electrode 104 can be prepared using a spray coating technique. Compressed air or ultrasonic atomization is used to spray a micro-mist of the electrode slurry onto the current collector 110. This process allows for the formation of a thin and uniform electrode layer, and is particularly suitable for large-scale production.

[0483] Cryogenic casting

[0484] Cryogenic casting is another potential method for manufacturing the negative electrode 104. This process involves freezing a slurry of electrode material, followed by sublimation of the ice to form a porous structure. The resulting porous electrode can then be sintered and attached to the current collector 110.

[0485] Sol-gel method

[0486] In some cases, the sol-gel method can be used to prepare the negative electrode 104. This method involves forming a colloidal suspension (sol), which is then transformed into a gel-like network containing the negative electrode active material and other components. This gel can be coated onto the current collector 110 and then heat-treated to form the final electrode structure.

[0487] vapor deposition

[0488] For specific applications, thin-film anodes can be directly formed on the current collector 110 using physical vapor deposition (PVD) or chemical vapor deposition (CVD) techniques. These methods can produce highly uniform and dense electrode layers, which are particularly advantageous for certain types of solid-state batteries.

[0489] Alloying and ball milling

[0490] Mechanical alloying and high-energy ball milling can be used to prepare composite anode materials, which can then be pressed into electrodes or coated onto current collector 110 using one of the aforementioned methods. This technique is particularly suitable for preparing nanostructured or amorphous anode materials with enhanced electrochemical performance.

[0491] Slurry method

[0492] For example, the negative electrode active material can be mixed with a solvent and optionally a binder and dispersant and stirred to form a slurry. The slurry can then be coated (e.g., coated) onto the current collector 110, followed by pressing and drying to obtain the negative electrode 104.

[0493] Coating method for negative electrode slurry

[0494] The coating of the negative electrode 104 slurry may include techniques selected from the group consisting of: slot coating, gravure coating, spin coating, spray coating, roller coating, curtain coating, extrusion, casting, screen printing, inkjet printing, spray printing, gravure printing, thermal transfer, letterpress printing, intaglio printing, offset printing, and combinations thereof. In addition to the above techniques, other methods for coating the negative electrode slurry onto the current collector may include doctor blade coating, dip coating, and meniscus coating.

[0495] Double-layer slot coating

[0496] Alternatively, a double-slit coating method can be used, which allows two different electrode materials to be simultaneously coated onto the current collector in a single operation. This method could potentially enable the construction of gradient structures within the electrode, thereby simultaneously optimizing electrochemical properties and mechanical performance.

[0497] Solvent for negative electrode slurry

[0498] The solvent used for forming the negative electrode 104 may contain water and / or organic solvents such as N-methylpyrrolidone (NMP), dimethylformamide (DMF), acetone, dimethylacetamide, dimethyl sulfoxide (DMSO), isopropanol, etc., or combinations thereof. Considering factors such as slurry coating thickness, productivity, etc., or combinations thereof, the solvent may be used in an amount sufficient to dissolve and disperse electrode components such as the negative electrode active material and binder. Other usable organic solvents include ethanol, methanol, propanol, butanol, ethyl acetate, methyl ethyl ketone, tetrahydrofuran, diethyl ether, and toluene.

[0499] Solvent-free method

[0500] In some embodiments, the negative electrode 104 may be prepared using solvent-free methods, such as dry powder processing or melt extrusion, which eliminates the need for liquid solvents and provides environmental and cost benefits.

[0501] Dispersant for negative electrode slurry

[0502] The dispersant forming the negative electrode 104 may include aqueous dispersants or organic dispersants, such as N-methyl-2-pyrrolidone. Other examples of aqueous dispersants may include sodium dodecyl sulfate (SDS), polyvinylpyrrolidone (PVP), and carboxymethyl cellulose (CMC), while other organic dispersants may include Triton X-100, polyethylene glycol (PEG), and various surfactants such as polysorbate or poloxamer.

[0503] Dispersant-free method

[0504] In some embodiments, the negative electrode 104 may be prepared using methods that do not require dispersants, such as dry powder processing or specific additive manufacturing techniques.

[0505] Drying technology for negative electrode slurry

[0506] The slurry for the negative electrode 104 can be dried by irradiation with heat, an electron beam (E-beam), gamma rays, or ultraviolet light (G / H / I lines), or a combination thereof, causing the solvent to vaporize. For example, the slurry can be vacuum dried at room temperature. Although the solvent is removed by evaporation through the drying step, other components do not evaporate and remain intact to form the negative electrode 104.

[0507] Other drying techniques

[0508] In addition to the drying techniques mentioned above, a variety of other methods can be used to dry the negative electrode slurry. Depending on the specific materials, production requirements, and desired electrode characteristics, these other techniques can offer various advantages.

[0509] Infrared (IR) drying

[0510] Infrared (IR) drying can be used to rapidly heat the electrode surface, promoting efficient solvent evaporation. This method is particularly effective for thin electrode coatings and allows for precise control of the drying process.

[0511] Microwave drying

[0512] Microwave drying is another option, which can provide volumetric heating of the electrode material, potentially producing more uniform drying across the entire electrode thickness. In some cases, a combination of convection and microwave drying can be used to simultaneously optimize drying speed and uniformity.

[0513] freeze-drying

[0514] For specific electrode formulations, freeze-drying (also known as lyophilization) can be used. This process involves freezing the slurry and then sublimating the solvent under vacuum conditions. Freeze-drying can help maintain the porous structure of the electrode, which can facilitate electrolyte permeation and ion transport.

[0515] Supercritical carbon dioxide drying

[0516] Supercritical CO2 drying is an advanced technique applicable to specialized electrode materials. This method involves replacing the solvent with liquid CO2, subsequently bringing it to a supercritical state, and then evacuating it. This process can help preserve the fine nanostructure within the electrode and is particularly suitable for aerogel electrodes.

[0517] Two-step drying

[0518] In some cases, a two-step drying method can be used. For example, the initial drying can be carried out at a lower temperature to remove most of the solvent, followed by a high-temperature step to remove the residual solvent and potentially initiate any desired chemical reactions within the electrode material.

[0519] Ultrasonic drying

[0520] For specific electrode formulations, ultrasonic drying can also be considered. This technique utilizes high-frequency sound waves to agitate solvent molecules, potentially accelerating the drying process and improving solvent removal from the porous structure within the electrode.

[0521] Overview of solid electrolyte layers

[0522] The solid electrolyte layer 106 is suitable for lithium-ion diffusion between the positive electrode 102 and the negative electrode 104. The solid electrolyte layer 106 provides a conductive path for the movement of charge carriers between the positive electrode 102 and the negative electrode 104. The solid electrolyte layer 106 is electrically connected to the positive electrode 102 and the negative electrode 104.

[0523] solid electrolyte position

[0524] In one embodiment, a solid electrolyte layer 106 is formed above and in direct contact with the positive electrode 102 or the negative electrode 104. In another embodiment, the solid electrolyte layer 106 is in direct contact with both the positive and negative electrodes 102 and 104. In other embodiments, other functional layers may be disposed between the solid electrolyte layer 106 and the positive and / or negative electrodes 104.

[0525] Materials for solid electrolyte layers

[0526] The solid electrolyte layer 106 is capable of transporting lithium ions. The material of the solid electrolyte layer 106 is not particularly limited, as long as it can adhere to adjacent layers, has suitable conductivity, and does not cause significant chemical changes in the solid-state battery 100 within the voltage range of the corresponding solid-state battery 100. For example, the solid electrolyte layer 106 may comprise various inorganic solid electrolytes, polymer solid electrolytes, and / or polymer gel electrolytes, but is not limited thereto. Additionally or alternatively, the solid electrolyte layer 106 may comprise ceramic electrolytes, glass electrolytes, organic-inorganic hybrid electrolytes, and nanostructured electrolytes, but is not limited to these types.

[0527] Inorganic solid electrolytes

[0528] Inorganic solid electrolytes can include, but are not limited to, crystalline solid electrolytes, amorphous solid electrolytes, glass-ceramic solid electrolytes, or combinations thereof. Inorganic solid electrolytes can be sulfide-based, oxide-based, or combinations thereof. Besides sulfide and oxide-based inorganic solid electrolytes, other types of inorganic solid electrolytes may also include halide electrolytes, nitride electrolytes, and borate electrolytes. For example, lithium-rich anti-perovskites such as Li3OCl and Li3OBr (LiRAP), lithium nitride (Li3N), and lithium borohydride (LiBH4) have been studied as potential solid electrolyte materials for lithium-ion batteries.

[0529] Sulfide solid electrolytes

[0530] Sulfide solid electrolytes contain sulfur (S) and have the ionic conductivity of metals belonging to Group 1 or Group 2 of the periodic table. They can include Li-PS type glasses or Li-PS type glass ceramics.

[0531] Examples of sulfide solid electrolytes

[0532] For example, sulfide-based solid electrolytes may include lithium sulfide, silicon sulfide, germanium sulfide, and boron sulfide. Specific examples of inorganic solid electrolytes may include Li. 3.833 Sn 0.833 As 0.166 S4, Li4SnS4, Li 3.25 Ge 0.25 P 0.75S4, Li2S-P2S0, B2S3-Li2S, 3+y PO 4-x N x ), thiolated LISICON (Li 3.25 Ge 0.25 P 0.75 S4), Li2O-Al2O3-TiO2-P2O5 (LATP), Li2S-P2S5, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5 , Li2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SnS, Li2S-P2S5-Al2S3, Li2S-GeS2, Li2S-GeS2-ZnS, Li 10 GeP2S 12 (LGPS), Li7P3S 11 , Li6PS5Cl, Li6PS5Br, Li6PS5I, Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 Li 11 Si2PS 12 etc. or combinations thereof.

[0533] Doped variants

[0534] In some cases, doped variants of these materials, such as Al-doped Li, can also be used. 10 GeP2S 12 Alternatively, Sb can be doped into Li6PS5Cl to further enhance ionic conductivity or stability.

[0535] Oxide solid electrolytes

[0536] Oxide-based solid electrolyte materials contain oxygen (O) and have the ionic conductivity of metals belonging to Group I or Group II of the periodic table.

[0537] Examples of oxide-based solid electrolytes

[0538] Oxide-based solid electrolyte materials may include at least one selected from the group consisting of: LLTO compounds, Li6La2CaTa2O 12 Li6La2ANb2O 12 (A is Ca or Sr), Li2Nd3TeSbO 12 Li3BO 2.5 N 0.5 Li9SiAlO8, LAGP compounds, LATP compounds, Li 1+x Ti 2-x Al x Si y (PO4) 3-y (0≤x≤1,0≤y≤1), LiAl x Zr 2-x (PO4)3(0≤x≤1,0≤y≤1), LiTi x Zr 2-x (PO4)3 (0≤x≤1, 0≤y≤1), LISICON-type compounds, LIPON-type compounds, perovskite-type compounds, NASICON-type compounds, and LLZO-type compounds or derivatives (such as Al-doped Li7La3Zr2O). 12 Ta-doped Li7La3Zr2O 12 Lithium-rich anti-perovskites such as Li3OCl and Li3OBr have been studied as potential oxide-based solid electrolytes.

[0539] Composite oxide electrolyte

[0540] In some cases, composite oxide electrolytes that combine multiple oxide materials, such as the LLZO-LATP complex, can be used to take advantage of the advantages of different oxide systems.

[0541] Polymer solid electrolyte

[0542] Polymer solid electrolytes are complexes of electrolyte salts and polymer resins, exhibiting lithium-ion conductivity. Polymer solid electrolytes may include polyether polymers, polycarbonate polymers, acrylate polymers, polysiloxane polymers, phosphazene polymers, polyethylene derivatives, olefin oxide derivatives, phosphate ester polymers, polylysine, polyester sulfides, polyvinyl alcohol, polyvinylidene fluoride, polymers containing ionically dissociable groups, polyethyleneimine (PEI), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyethylene succinate (PES), chitosan, and cellulose derivatives, as well as other biopolymers or combinations thereof.

[0543] Polymer resin for solid polymer electrolytes

[0544] Solid polymer electrolytes may contain polymer resins, such as branched copolymers of the polyethylene oxide (PEO) backbone containing comonomers copolymerized with amorphous polymers such as PMMA, polycarbonate, polysiloxane (PDMS) and / or phosphazene, comb polymers, crosslinked polymer resins, polyethylene glycol (PEG), polypropylene oxide (PPO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), ethylene oxide-propylene oxide copolymer (PEO-PPO), polyethyleneimine (PEI), polyvinylpyrrolidone (PVP), polyvinyl alcohol (PVA), various block copolymers or graft copolymers containing these materials, or combinations thereof.

[0545] Polymer gel electrolyte

[0546] Polymer gel electrolytes can be formed by incorporating organic electrolytes containing organic solvents and electrolyte salts, ionic liquids, monomers or oligomers into polymer resins or combinations thereof. Polymer resins used for polymer gels may include polyether polymers, PVC polymers, PMMA polymers, polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), or combinations thereof.

[0547] Examples of polymer gel electrolytes

[0548] Examples of polymeric gel electrolytes suitable for solid-state batteries include polyethylene oxide (PEO), methyl methacrylate-ethyl acrylate copolymer (PMMA-EA), acrylonitrile-methyl methacrylate copolymer (PAN-MMA), polyvinyl acetate (PVAc), polyethylene glycol diacrylate (PEGDA), polyvinylpyrrolidone (PVP), polyethylene glycol methyl ether acrylate (PEGMEA), polyethylene glycol methyl ether methacrylate (PEGMEMA), polyionic liquid (PIL), ethylene glycol-propylene glycol copolymer (PEG-PPG), ethylene alcohol-ethylene copolymer (PVA-PE), polyacrylamide (PAM), poly(2-hydroxyethyl methacrylate) (PHEMA), ethylene glycol-ethylene oxide copolymer (PEG-PEO), and polymethacrylic acid (PMAA) gel electrolytes to optimize the electrochemical and physical properties of solid electrolytes.

[0549] Electrolyte salts

[0550] Electrolyte salts are ionizable lithium salts, which can be converted from Li... + X - Indicates. X - It can include the option F. - Cl - ,Br - NO3- N(CN)2 - BF4 - ClO4 - AlO4 - AlCl4 - PF6 - SbF6 - AsF6 - BF2C2O4 - BC4O8 - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - CF3SO3 - C4F9SO3 - CF3CF2SO3 - (CF3SO2)2N - (F2SO2)2N - CF3CF2(CF3)2CO - (CF3SO2)2CH, CF3(CF2)7SO3 - CF3CO2 - CH3CO2 - SCN - (CF3CF2SO2)2N - Anions in the group composed of, etc.

[0551] Examples of lithium salts

[0552] For example, the lithium salt can be selected from LiTFSI, LiCl, LiBr, LiI, LiClO4, lithium tetrafluoroborate (LiBF4), LiB 10 Cl 10The electrolyte salt may be any one of the following groups: lithium hexafluorophosphate (LiPF6), LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3CO2, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC4F9SO3, LiC(CF3SO2)3, (CF3SO2)2NLi, lithium chloroborate, lower aliphatic carboxylic acids, lithium 4-phenylborate imide, lithium dioxolane borate (LiBOB), lithium difluorooxolane borate (LiDFOB), lithium bis(fluorosulfonyl)imide (LiFSI), lithium 4,5-dicyano-2-(trifluoromethyl)imazole (LiTDI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), etc. The electrolyte salt may comprise any combination of the salts described in this application.

[0553] Amount of electrolyte salts

[0554] Based on the total weight of the solid electrolyte layer 106, the solid electrolyte layer 106 may contain 0, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, or 400 parts or approximately of electrolyte salt. In an embodiment, based on the total weight of the solid electrolyte layer 106, the electrolyte salt in the solid electrolyte layer 106 may be within a range formed by selecting any two values ​​listed above, or selecting approximately 0 parts to approximately 400 parts, or approximately 60 parts to approximately 400 parts.

[0555] Ion conductivity of solid electrolyte layers

[0556] The solid electrolyte layer 106 may possess suitable reduction stability and / or ionic conductivity. Since the solid electrolyte layer 106 primarily functions to transport lithium ions between electrodes, it may possess, for example, 10... -7 S / cm, 10 -6 S / cm, 10 -5 S / cm or 10 -4 S / cm, which is around or exceeds its ideal ionic conductivity.

[0557] Thickness of solid electrolyte layer

[0558] The thickness t6 of the solid electrolyte layer 106 can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 44 0, 450, 460, 470, 480, 490, 500, 510, 520, 530, 540, 550, 560, 570, 580, 590, 600, 610, 620, 630, 640, 650, 660, 670, 680, 690, 700, 710, 720, 730, 740, 750, 760, 770, 780, 790, 800, 810, 820, 830, 840, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950, 960, 970, 980, 990 or 1,000 μm or approximately thereafter. In an embodiment, the thickness t6 of the solid electrolyte layer 106 can be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​in the range of 0 μm to 1000 μm, for example, about 5 μm to 1000 μm, about 30 μm to 100 μm, or about 30 μm to 50 μm.

[0559] Unfinished products

[0560] The cell 101 shown in Figure 1 can be provided as an unfinished product. In one embodiment, the cell 101 can be stored, transported, and / or delivered to distributors, customers, etc., for whom the manufacture of a battery assembly or product incorporating the cell 101 is completed. In other embodiments, the cell 101 is a finished battery assembly or product.

[0561] Sealed battery

[0562] The solid-state battery casing 112 can be sealed to complete the manufacture of the solid-state battery 100, enabling it to function as a battery. The sealing process can be designed with various techniques to ensure that internal components are protected from external environmental factors and to maintain the integrity of the battery structure. For example, methods such as laser welding, ultrasonic welding, or adhesive bonding can be used to achieve an airtight seal for the casing 112. In some cases, the sealing process may also include introducing a protective atmosphere or removing air to create a vacuum within the casing. This sealing step can help prevent the intrusion of moisture that could potentially degrade the performance of sulfide-based solid electrolytes. Furthermore, the encapsulation process can incorporate safety features such as pressure relief mechanisms to manage any potential gas buildup during battery operation.

[0563] After the battery is sealed

[0564] After proper sealing, the solid-state battery 100 can undergo final quality control checks, including electrical testing, leak detection, and visual inspection. Following these checks, the solid-state battery 100 can be packaged and sold as a finished product, and then integrated into various electronic devices, electric vehicles, energy storage systems, etc.

[0565] Battery composition

[0566] Solid-state battery 100 is provided in various configurations to suit different applications and device requirements. In some cases, the battery can be manufactured in a cylindrical shape, which can be advantageous for certain types of portable electronic devices or automotive applications. Alternatively, solid-state battery 100 can be manufactured in a prismatic shape, which allows for more efficient space utilization within devices with a rectangular form factor. In other cases, a pouch shape can be adopted, providing flexibility in form and potentially reducing the overall weight of the battery. Pouch shapes are further particularly suitable for solid-state batteries because it is easier to apply and control uniform pressure within the battery.

[0567] Choice of composition

[0568] The choice of configuration can depend on factors such as intended use, space constraints, thermal management requirements, and manufacturing considerations. In some implementations, hybrid or custom configurations combining different forms of elements may be utilized, if necessary. The diversity of battery form factors enables the integration of solid-state batteries into a wide range of products, from small wearable devices to large energy storage systems.

[0569] Voltage

[0570] The solid-state battery 100 is configured to output 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 35, 40, 45, 48, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 96, 100, 110, 120. Voltages of 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, or 500 V or approximately thereof. In an embodiment, the output voltage of the solid-state battery 100 can be within a range formed by selecting any two values ​​listed above or by selecting any two values ​​in the range from 0 to 500 V, for example, from approximately 1 V DC to approximately 500 V DC.

[0571] capacity

[0572] The solid-state battery 100 can be configured to have a capacity of 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, or 300 mAh / g, or greater thereon. In an embodiment, the output voltage of the solid-state battery 100 can have a capacity formed by selecting any two values ​​listed above or by selecting any two values ​​within the range of 0 to 300 mAh / g or 0 to approximately 300 mAh / g, for example, approximately 100 mAh / g to approximately 300 mAh / g.

[0573] Volume expansion calculation

[0574] The solid-state battery 100 can be configured to have an ideal volumetric expansion rate. The volumetric expansion rate can be calculated from the change in thickness after the first charge-discharge cycle compared to the initial thickness. The volumetric expansion rate can be the ratio of the thickness change to the initial thickness. The first charge-discharge cycle is performed by charging the battery at 0.1 C CC-CV and cutting off at 4.25 to 4.4 V and 0.02 C, and then discharging the battery at 0.1 C CC and cutting off at 3 V. The volumetric expansion rate is calculated using the following mathematical formula 1, where A can represent the thickness before charge-discharge, and B can represent the thickness after charge-discharge. The thickness can be measured using a Mauser micrometer or a scanning electron microscope (SEM).

[0575] Mathematical formula 1: Volume expansion rate = [( BA ) / A ]×100

[0576] C-fold

[0577] The C-rate used in this application refers to the rate of discharge of a battery relative to its maximum capacity. For example, a 1C rate means that the discharge current will discharge the entire battery in one hour. That is, for a 20 Ah battery, a 1C discharge current is 20 Amps.

[0578] Battery C-rate

[0579] The solid-state battery 100 may have a C-rate of 0.33, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, or 5, or greater than such a rate. In an embodiment, the C-rate of the solid-state battery 100 may be within a range formed by selecting any two values ​​listed in the preceding sentence, for example, from about 0.33 to about 5.

[0580] Other examples of volume expansion

[0581] Other methods for measuring and calculating the volume expansion rate of solid-state batteries may include volume expansion measurement methods (such as gas gravity method), in-situ expansion measurement methods, X-ray tomography, strain gauge measurement methods, optical methods (such as digital image correlation or laser interferometry), pressure-based methods, and electrochemical strain microscopy.

[0582] contradiction

[0583] Other features, implementation methods, and examples described below apply to various aspects of the invention described above. However, in the event of any contradiction between the information in the foregoing discussion and the information in the following discussion, the information in the foregoing section shall prevail.

[0584]

Example

[0585] Example

[0586] Embodiments will be described more fully below to facilitate a better understanding of this disclosure. However, the following embodiments are for illustrative purposes only, and the scope of this disclosure is not limited thereto.

[0587] Example 1: Manufacturing composite materials

[0588] Example 1-1: Manufacturing a composite material containing LPSCl

[0589] The positive electrode, composed of active materials such as Li₂S, was purchased from Sigma-Aldrich. The solid electrolyte material LPSCl was obtained from NEI and milled using a planetary ball mill before use. Acetylene black (AB) carbon, used as a conductive agent, was obtained from Sigma-Aldrich. Both Li₂S and AB were dried overnight under vacuum at 80°C to remove excess moisture. Scanning electron microscopy (SEM) analysis was performed on these materials to confirm their morphology and dimensions before and after ball milling.

[0590] For both powders and pellets, SEM was performed on a FEI Apreo and / or FEI Scios dual-beam focused ion beam (FIB) / SEM with an accelerating voltage of 5 kV and a beam current of 0.1 nA. Powder and pellet samples were prepared in an argon-filled glove box and transferred via a hermetically sealed transfer arm to avoid any air contact. For FIB cross-sectional images, milling was performed under cryogenic conditions (-180°C) using gallium as the ion beam source. Parameters used for all milling conditions were 30 kV and 65 nA, with subsequent cross-sectional cleaning performed at 30 kV and 15 nA.

[0591] Figure 3A This is a SEM image of the obtained Li2S particles. Figure 3B This is an SEM image of ground LPSCl particles. Figure 3C This is a SEM image of AB carbon. The obtained Li2S material was milled in an airtight zirconia jar using zirconia-stabilized grinding media with high-energy ball milling at 400 RPM for 10 hours, reducing its size from approximately 30 μm to approximately 1 μm. Figure 3D It is the original Li2S material in combination with Figure 3A SEM images at different magnifications. Figure 3E This is an SEM image of the ground Li2S material, showing a reduced particle size for better contrast with the composite material.

[0592] Subsequently, 30 wt% Li2S, 20 wt% carbon and 50 wt% LPSCl were manually mixed with a mortar and pestle, and then mixed with grinding media and grinding balls in a grinding container and ground at 500 RPM for 1 hour. Figure 4 This is a diagram of a ball mill.

[0593] Examples 1-2: Manufacturing composite materials containing LPSF

[0594] Except for replacing LPSCl with LPSF, repeat Examples 1-1.

[0595] Examples 1-3: Manufacturing composite materials containing LPSBr

[0596] Repeat Examples 1-1 except that LPSBr is used instead of LPSCl.

[0597] Examples 1-4: Manufacturing composite materials containing LPSI

[0598] Except that LPSI is used instead of LPSCl, repeat Examples 1-1.

[0599] Example 2: Characterization of composite materials

[0600] Example 2-1: X-ray diffraction

[0601] XRD measurements were collected using a Bruker SMART instrument in the Department of X-ray Crystallography at the University of California, San Diego, using Mo Kα (λ = 0.71 Å) radiation and a platinum-135 CCD detector. Measurements were performed at 2θ from 5 to 90° and collected at ambient temperature. Samples were prepared using 0.7 mm boron capillaries in an argon-filled glove box and flame-sealed to ensure airtightness measurements of sensitive samples.

[0602] XRD analysis was performed on ground Li₂S / LPSCl / C mixtures, ground Li₂S / LPSCl mixtures, LPSCl, and Li₂S, respectively. Samples were prepared in an argon glove box by loading the ground composite powder into 0.5–0.7 mm boron-rich capillaries, followed by flame sealing for airtightness measurements. XRD measurements were collected in the 2θ range from 5 to 50° on a Bruker Apex II-Ultra CCD microfocusing rotating anode instrument equipped with a Mo Kα (λ = 0.7107 Å) radiation source.

[0603] Figure 5 XRD results for the milled Li₂S / LPSCl / C mixture, the milled Li₂S / LPSCl mixture, LPSCl, and Li₂S are shown. These results show that no LPSCl XRD peak is present in the milled Li₂S / LPSCl / C mixture, indicating that the crystallinity of LPSCl in the milled composite is at least reduced. Linear combination fitting (LCF) results show that half of the LPSCl is converted to LPS after the milling process. XRD results also show that no LPS XRD peak is present in the milled Li₂S / LPSCl / C mixture, indicating that the LPS present in the milled composite has low or nanocrystalline properties. To eliminate any possibility of feature masking, the XRD of the carbon-free composite was also measured, where a small broad peak was detected at 2θ at 13.7°. This could be attributed to the main diffraction peak (311) of LPSCl or the main diffraction peak (211) of β-LPS, both of which are present at 2θ at 13.7°.

[0604] Example 2-2: Synchrotron X-ray Absorption Spectroscopy (XAS)

[0605] Soft X-ray absorption spectroscopy (XAS) measurements were performed on beamline 16A1 of the Taiwan Light Source (TLS) at the Synchrotron Radiation Research Center (SRRC) in Hsinchu, Taiwan. This beamline used a dual-crystal Si (111) monochromator for photon energies from 2 to 8 keV. All samples were sealed in 2.5 μm thick Mylar® film bags within an argon-filled glove box to prevent air exposure. Each sample was mounted on a sample holder and placed in the measurement chamber at a 45° angle relative to the incident X-ray beam. The chamber was continuously flushed with helium for at least 45 minutes before XAS data acquisition to reduce X-ray attenuation. Sulfur K-edge X-ray absorption near-edge structure (XANES) spectra were acquired using a Lytle detector in Total Fluorescence Yield (TFY) mode with a scan step of 0.2 eV. The photon energies of the SK-edge were calibrated to 2472 eV (maximum of the first derivative) using elemental sulfur. Background subtraction, normalization, and linear combination fitting (LCF) of the XANES spectra were performed using Athena software.

[0606] The composite material manufactured in Example 1-1 was subjected to synchrotron radiation XAS. Figures 6A to 6F Synchrotron radiation XAS results of the composite material prepared in Example 1-1 are shown. Figure 6A For reference spectrum, Figures 6B to 6D XAS of the original, charged and discharged (after 1 cycle) composite material is shown. Figure 6E This is the original spectrum of the SK edge. Figure 6F The linear combination fitting results are shown. The results indicate that the complex remains reversible despite LPSCl degradation. After discharge, peaks attributed to Li₂S from the reference spectrum were observed at 2474.2 eV and 2476.8 eV, accompanied by a significant attenuation of the elemental sulfur peak, which is in good agreement with the XRD results. After charging, the characteristic peaks attributed to Li₂S disappeared, and an enhancement of the elemental sulfur peak was observed. The reversibility of the Li₂S cathode when paired with LPSCl is unmistakable. After charging, the characteristic peaks attributed to α-sulfur were prominent at 2473.6 eV and 2480 eV, while the intensity of the characteristic peaks attributed to Li₂S decreased. After discharge, the spectrum returned to its original state, with the clear characteristic peaks attributed to Li₂S at 2474.2 eV and 2476.8 eV reappearing. The LCF results show that the original sample was half LPSCl and half LPS. 27.5% by weight of LPS was detected in its original state, indicating that some LPSCl had decomposed. This is consistent with... Figure 5The XRD patterns were consistent with those observed, but the undetectable diffraction peaks associated with LPSCl indicated reduced crystallinity or decomposition. The results showed that the LPS / LPSCl mixture retained its ionic conductivity and could act as a catalyst to mediate the oxidation of Li₂S. This was confirmed in charged LCF results, where Li₂S was highly utilized, forming more sulfur than expected due to LPS oxidation, but almost returning to its original state. These results support the excellent reversibility of the lithium-sulfur system, attributed to the oxidation-mediating function of the LPSCl electrolyte.

[0607] Example 3: Manufacturing the positive electrode

[0608] Example 3-1: Fabrication of a positive electrode containing LPSCl

[0609] The ball-milled cathode composite material from Examples 1-1 was pressed at 375 MPa in a custom cell fixture to manufacture a cathode for solid-state batteries. The cathode loading can be adjusted according to the target battery capacity.

[0610] Example 3-2: Manufacturing a positive electrode containing LPSF

[0611] Except for using the composite materials from Examples 1-2, Examples 3-1 were repeated.

[0612] Example 3-3: Fabrication of a positive electrode containing LPSBr

[0613] Examples 3-1 were repeated except that the composite materials from Examples 1-3 were used.

[0614] Examples 3-4: Manufacturing a positive electrode containing LPSI

[0615] Examples 3-1 were repeated except that the composite materials from Examples 1-4 were used.

[0616] Example 4: Manufacturing an all-solid-state battery

[0617] Example 4-1: Manufacturing a battery using a positive electrode containing LPSCl

[0618] To fabricate an all-solid-state battery, the composite cathode from Example 3-1, the solid electrolyte LPSCl layer, and the Li... 0.5 Anodes composed of in alloys or silicon are pressed together under varying pressure in a plunger cell to manufacture an all-solid-state battery, such as... Figure 7 As shown. First, 50 to 75 mg of LPSCl was pressed at 75 MPa to form a separator layer. Then, positive and negative electrode powders were added to both sides of the separator layer and pressed to 75 MPa.

[0619] Example 4-2: Manufacturing a battery using a positive electrode containing LPSF

[0620] Except for using the composite positive electrode of Example 3-2, Example 4-1 was repeated.

[0621] Example 4-3: Manufacturing a battery using a positive electrode containing LPSBr

[0622] Except for using the composite positive electrode of Example 3-3, Example 4-1 was repeated.

[0623] Example 4-4: Manufacturing a battery using a positive electrode containing LPSI

[0624] Except for using the composite positive electrode of Examples 3-4, Examples 4-1 were repeated.

[0625] Example 5: Two-step grinding

[0626] Example 5-1: Two-step milling of 40% Li2S / LiI and LPS

[0627] The mixture of Li2S and LiI was ground together at 500 RPM, followed by the grinding of solid electrolyte LPS at 300 RPM.

[0628] Example 5-2: Two-step grinding of 40% Li2S / LiI and LPSCl

[0629] Except that LPS is replaced with LPSCl, Example 5-1 is repeated.

[0630] Example 5-3: Two-step grinding of 30% Li2S / LiI and LPSCl

[0631] Except that the weight percentage of Li2S in the composite material is 30%, Examples 5-2 are repeated.

[0632] Example 5-4: Manufacturing batteries using 40% Li2S / LiI / LPS composite material

[0633] Example 4 was repeated using the composite material from Example 5-1.

[0634] Example 5-5: Manufacturing batteries using 40% Li2S / LiI / LPSCl composite material

[0635] Examples 5-4 were repeated except that the composite material of Example 5-1 was replaced with the composite material of Example 5-2.

[0636] Examples 5-6: Manufacturing batteries using 30% Li2S / LiI / LPSCl composite material

[0637] Examples 5-4 were repeated except that the composite material of Example 5-1 was replaced with the composite material of Example 5-3.

[0638] Examples 5-7: Measurement of the specific capacity of batteries containing 40% Li₂S / LiI / LPS composite material

[0639] The specific capacity of the batteries in Examples 5-4 was measured by applying a constant current with a cutoff voltage between an upper cutoff voltage of 3V and a lower cutoff voltage of 1.3V. The batteries were tested at room temperature and 75 MPa using Li 0.5 Cycling is performed at the negative electrode. Capacity utilization and cell cycling are evaluated using a Neware Instrument cycler (CT-4008T). Figure 8 The results show that the battery containing LiI and LPS in the positive electrode exhibits high polarization and low utilization due to the limited ionic conductivity of LPS, resulting in slow conversion kinetics of Li2S.

[0640] Examples 5-8: Measurement of the specific capacity of batteries containing 40% Li₂S / LiI / LPSCl composite material

[0641] Repeat Examples 5-7 for the batteries of Examples 5-5. Figure 9 The voltage curves of the battery using LPSCl instead of LPS are shown. Improved utilization and reduced cell polarization are achieved due to the improved mechanical properties and ion conductivity of LPSCl, resulting in better interfacial contact between all components (Li₂S, carbon materials, LPSCl) for Li₂S conversion. However, the addition of LiI to the composite material still leads to a Li₂S utilization rate lower than the theoretical value (600 mAh g⁻¹). -1 vs 1200 mAh g -1 ).

[0642] Examples 5-9: Measurement of the specific capacity of batteries containing 30% Li₂S / LiI / LPSCl composite material

[0643] Repeat Examples 5-7 for the batteries of Examples 5-6. Figure 10 The specific capacity measured for this battery is shown. Compared to the batteries in Examples 5-4 and 5-5, this battery uses more solid electrolyte material to improve ionic conductivity, thus improving battery utilization. However, due to the instability of the Li₂S / LiI / LPSCl composite, the battery still exhibits poor cycle stability, indicating mechanical and electrochemical degradation. The addition of LiI to the composite leads to poor cycle stability, possibly hindering sites for Li₂S conversion and resulting in insufficient conductive network.

[0644] Example 6: Mixing Method

[0645] Example 6-1: Manufacturing composite materials by manual mixing

[0646] The hand-mixed composite material is manufactured by mixing Li2S cathode, carbon, and LPSCl in a mortar and pestle for an extended period of 30 to 60 minutes, depending on the batch size.

[0647] Example 6-2: Manufacturing composite materials by one-step ball milling

[0648] Example 1-1 was repeated using Li₂S, carbon, and LPSCl solid electrolyte. The powders were mixed manually with a mortar and pestle, and then ground at 500 RPM for 1 hour using 5 mm grinding media at a batch-to-ball ratio of 30:1. Prolonged grinding times lead to degradation of the LPSCl solid electrolyte, disrupting conduction pathways and causing a decrease in ionic conductivity.

[0649] Example 6-3: Manufacturing composite materials via two-step ball milling

[0650] Example 5-1 was repeated using Li2S, carbon, and LPSCl. First, the Li2S cathode was milled together with carbon at 500 RPM for 1 hour. Then, the LPSCl solid electrolyte was mixed with the Li2S / carbon composite and lightly milled at 300 RPM for 30 minutes.

[0651] Example 6-4: Manufacturing batteries using composite materials prepared by hand mixing

[0652] Example 4 was repeated using the composite material from Example 6-1.

[0653] Examples 6-5: Manufacturing batteries using composite materials prepared by one-step ball milling

[0654] The composite material from Example 6-2 was used to repeat Example 6-4.

[0655] Examples 6-6: Manufacturing batteries using composite materials prepared by two-step ball milling

[0656] The composite material from Examples 6-3 was used to repeat Examples 6-4.

[0657] Examples 6-7: Measuring the specific capacity of the batteries from Examples 6-4

[0658] Repeat Examples 5-7 for the batteries of Examples 6-4.

[0659] Examples 6-8: Measuring the specific capacity of the batteries from Examples 6-5

[0660] Repeat Examples 5-7 for the batteries of Examples 6-5.

[0661] Examples 6-9: Measuring the specific capacity of the batteries from Examples 6-6

[0662] Repeat Examples 5-7 for the batteries of Examples 6-6.

[0663] Figure 11 It was shown at 0.05 mA cm-2 A comparison of the specific capacities of the batteries of Examples 6-4, 6-5, and 6-6 obtained at a given current density was presented. The results show that the mixing method of the electrode composite material significantly affects the specific capacity / utilization of the Li2S cathode, and consequently, the energy output and electrochemical performance of the battery using the electrode composite material of Example 6-2. It is evident that the process of Example 6-2 produces additional properties from the LPSCl solid electrolyte during battery discharge. Here, LPSCl undergoes electrochemical reduction, potentially forming Li2S and LPS, which contributes to battery capacity and stable cycle performance.

[0664] Example 7: Halogen solid electrolyte

[0665] Example 7-1: Manufacturing composite materials

[0666] Except for replacing LPSCl with Li3YCl6 (LYC), repeat Examples 1-1.

[0667] Example 7-2: Manufacturing the positive electrode

[0668] The composite material prepared in Example 7-1 was used to repeat Example 3-1.

[0669] Example 7-3: Manufacturing a battery using a Li-In alloy anode

[0670] The positive electrode prepared in Example 7-2 was used to repeat Example 4-1.

[0671] Example 7-4: Manufacturing a battery using a Si negative electrode

[0672] Except for using a Si negative electrode, repeat Examples 7-3.

[0673] Example 7-5: Measuring specific capacity

[0674] The batteries manufactured in Examples 7-3 and 7-4 were repeated in Examples 5-7. Figure 12 The specific capacity and poor cycle stability of the batteries manufactured in Examples 7-3 are shown after repeated cycling. Figure 13 The specific capacity measured for the batteries manufactured in Examples 7-4 is shown. The use of a Si anode resulted in higher cell resistance, likely due to the poor mechanical properties of LYC (low elastic modulus and compactness). The results showed significant capacity loss despite the use of LYC. This is attributed to the lack of reduction stability of LYC during battery discharge, leading to decreased ion conductivity within the composite.

[0675] Example 8: Positive Electrode Formulation

[0676] Example 8-1: Manufacturing a composite material with 30% Li2S

[0677] Example 1-1 was repeated with Li2S accounting for 30% of the total weight of the composite material.

[0678] Example 8-2: Manufacturing a composite material with 35% Li2S

[0679] Example 1-1 was repeated with Li2S accounting for 35% of the total weight of the composite material.

[0680] Example 8-3: Manufacturing a composite material with 40% Li2S

[0681] Example 1-1 was repeated with Li2S accounting for 40% of the total weight of the composite material.

[0682] Example 8-4: Manufacturing a composite material with 50% Li2S

[0683] Example 1-1 was repeated with Li2S accounting for 45% of the total weight of the composite material.

[0684] Examples 8-5: Manufacturing composite materials with 60% Li2S

[0685] Example 1-1 was repeated with Li2S accounting for 60% of the total weight of the composite material.

[0686] Examples 8-6: Manufacturing composite materials with 70% Li2S

[0687] Example 1-1 was repeated with Li2S accounting for 70% of the total weight of the composite material.

[0688] Example 8-7: Manufacturing the positive electrode

[0689] Example 3-1 was repeated using the composite materials manufactured in Examples 8-1 to 8-6.

[0690] Example 8-8: Manufacturing a Battery

[0691] The positive electrode prepared in Examples 8-7 was used to repeat Example 4-1.

[0692] Examples 8-9: Measuring specific capacity

[0693] The batteries manufactured in Examples 8-8 were repeated in Examples 7-4. Figure 14 The specific capacity of the cells with 30, 35, and 40% by weight of Li2S is shown. Figure 15The specific capacities measured for batteries with 50, 60, and 70 wt% Li₂S are shown. These results indicate that the suitable weight percentage range for Li₂S is 30–40 wt%, at which point a slight decrease in capacity is observed; while with more than 40 wt% Li₂S, the battery fails to cycle, likely due to insufficient ion conduction network at the cathode caused by the limited volume of LSPCl. Due to the volume shrinkage and expansion of Li₂S during charge and discharge, the sufficient volume provided by the solid electrolyte is necessary to accommodate these volume changes within the cathode composite and maintain interfacial contact for lithium-ion conduction. This is why a 30–40 wt% composition achieves higher utilization and improved electrochemical performance.

[0694] Included combinations and features

[0695] This specification describes various features and characteristics to provide an understanding of the composition, structure, production, function, and / or operation of this disclosure, including the disclosed compositions, coatings, and methods. It should be understood that the various features and characteristics of this disclosure described herein can be combined in any suitable manner, whether or not such features and characteristics are explicitly described as combinations herein. The inventors and the applicant expressly intend that combinations of such features and characteristics be included within the scope of this disclosure as set forth in this specification. Therefore, the claims may be modified to state any feature and characteristic expressly or inherently recited or otherwise expressly or inherently supported in this specification in any combination. Furthermore, the applicant reserves the right to amend the claims to expressly waive features and characteristics that may be present in the prior art (even if such features and characteristics are not expressly described in this specification). Therefore, any such amendment will not add new information to this specification or the claims and will comply with the requirements of written description, sufficient disclosure, and addition.

[0696] References merged

[0697] Any patent, publication, or other document mentioned in this specification is incorporated herein in its entirety, unless otherwise stated, but only to the extent that the incorporated material does not contradict any existing descriptions, definitions, statements, illustrations, or other disclosures expressly set forth in this specification. Therefore, to the extent necessary, the explicit disclosures set forth in this specification shall supersede any contradictory material incorporated by reference. Any material or portion thereof incorporated by reference that contradicts any existing definitions, statements, or other disclosures set forth in this application shall be incorporated only to the extent that the incorporated material does not contradict existing disclosures. The applicant reserves the right to amend this specification to expressly represent any incorporated subject matter or portion thereof. Modifications to this specification incorporating such incorporated subject matter will comply with the requirements of written description, full disclosure, and addition.

[0698] Explanation from all aspects

[0699] While this disclosure provides descriptions of various specific aspects to illustrate different aspects of this disclosure and / or its potential applications, it should be understood that various changes and modifications can be made by those skilled in the art. Therefore, this disclosure should be understood as having the broad scope defined at least as claimed, and not as narrowly limited as the specific exemplary aspects provided in this application.

Claims

1. A method for manufacturing an electrode composite material, the method comprising: A mixture comprising Li2S particles, carbon particles, and LPSCl particles containing a lithium phosphorus sulfide (LPSCl) compound is provided in a ball mill container, wherein the LPSCl particles are crystalline, the crystallinity of which can be confirmed by XRD of the LPSCl particles or the mixture exhibiting the following XRD peaks: XRD peak (111) at 2θ 7.5°, XRD peak (200) at 2θ 8°, XRD peak (220) at 2θ 12°, XRD peak (311) at 2θ 13.5°, and XRD peak (222) at 2θ 14.5°, wherein the mixture does not contain LPS particles made of a lithium phosphorus sulfide (LPS) compound; and The mixture is ball-milled in the ball milling container to provide a ball-milled composite material, such that at least a portion of the LPSCl compound contained in at least a portion of the LPSCl particles is converted into an LPS compound, and further such that the XRD of the ball-milled composite material does not show an XRD peak (111) at 2θ 7.5°, an XRD peak (200) at 2θ 8°, an XRD peak (220) at 2θ 12°, an XRD peak (311) at 2θ 13.5°, and an XRD peak (222) at 2θ 14.5°.

2. The method as described in claim 1, wherein, The ball-milled composite material comprises solid electrolyte (SSE) particles, wherein the SSE particles comprise a first particle containing only the LPSCl compound, a second particle containing only the LPS compound, and a third particle containing both LPS and LPSCl compounds.

3. The method as described in claim 1, wherein, The XRD of the ball-milled composite material does not show an XRD peak (211) located at 2θ of 13.7°, which indicates the crystallinity of the LPS compound.

4. The method of claim 1, wherein, The mixture is essentially composed of the Li2S particles, the LPSCl particles, and the carbon particles.

5. The method of claim 1, wherein, The mixture consists of the Li2S particles, the LPSCl particles, and the carbon particles.

6. The method of claim 1, wherein, The Li2S particles after ball milling of the mixture have a particle size of 100 nm to 1 μm.

7. The method of claim 1, wherein, The carbon particles comprise one of the following groups: acetylene black (AB) carbon, vapor-grown carbon fiber (VGCF), carbon nanotubes (CNT), Ketjen black (KB) carbon, and combinations thereof.

8. The method of claim 1, wherein, The ball mill converts 30% to 70% by weight of the LPSCl compound into the LPS compound.

9. The method of claim 1, wherein, The mixture prior to the ball milling comprises: The total weight of the mixture is 20% to 40% by weight of Li2S particles; and The mixture contains 15% to 20% carbon particles by weight.

10. The method of claim 1, wherein, The mixture was ball-milled at 300 to 550 RPM for 1 minute to 20 hours.

11. The method of claim 1, wherein, The mixture prior to the ball milling comprises: Based on the total weight of the mixture being 20% ​​to 40% by weight of Li2S particles, and The total weight of the mixture is 15% to 20% carbon particles; The carbon particles comprise one of the following: acetylene black carbon, vapor-grown carbon fibers, carbon nanotubes, Ketjen black, and combinations thereof. The LPSCl particles before ball milling have a particle size of 1 μm to 30 μm. The particle size of the Li2S particles before ball milling is 250 nm to 25 μm. The mixture is ball-milled at 300 to 550 RPM for 1 to 5 hours; and The ball milling process converts 30% to 70% by weight of the LPSCl compound into the LPS compound.

12. The method of claim 1, wherein, The mixture prior to the ball milling comprises: Based on the total weight of the mixture being 25% to 35% by weight of Li2S particles, and The total weight of the mixture is 18% to 20% carbon particles; The carbon particles include acetylene black carbon; The mixture is ball-milled at 400 to 500 RPM for 1 to 5 hours; and The ball milling process converts 40% to 60% by weight of the LPSCl compound into the LPS compound.

13. An electrode composite material, comprising: Li2S particles containing Li2S compounds; Carbon particles; and Solid electrolyte (SSE) particles, said solid electrolyte (SSE) particles comprising a first particle containing only lithium phosphorus sulfide (LPSCl) compound, a second particle containing only lithium phosphorus sulfide (LPS) compound, and a third particle containing both LPS and LPSCl compounds. in, The XRD of the electrode composite material does not show XRD peaks (111) at 2θ 7.5°, (200) at 2θ 8°, (220) at 2θ 12°, (311) at 2θ 13.5°, and (222) at 2θ 14.5°, which indicate crystallized LPSCl.

14. The electrode composite material as described in claim 13, wherein, The XRD of the electrode composite material does not show an XRD peak (211) located at 2θ of 13.7°, which indicates the crystallinity of the LPS compound.

15. The electrode composite material of claim 13, comprising: The electrode composite material comprises 20% to 40% by weight of Li₂S particles; and The total weight of the electrode composite material is 15% to 20% carbon particles.

16. The electrode composite material as described in claim 13, wherein, The Li2S particles have a particle size of 100 nm to 1 μm.

17. The electrode composite material as described in claim 13, wherein, The carbon particles comprise one of the following groups: acetylene black (AB) carbon, vapor-grown carbon fiber (VGCF), carbon nanotubes (CNT), Ketjen black (KB) carbon, and combinations thereof.

18. The electrode composite material as described in claim 13, wherein, The carbon particles contain acetylene black carbon.

19. The electrode composite material as described in claim 13, wherein, The BET specific surface area of ​​the carbon particles is 70 m². 2 g -1 .

20. An electric vehicle comprising an all-solid-state battery, the all-solid-state battery comprising: The positive electrode comprises the electrode composite material of claim 13; Negative electrode; and A solid electrolyte layer is disposed between the positive electrode and the negative electrode and is configured to enable the transfer of lithium ions between the positive electrode and the negative electrode.